Absorbent, water absorbing agent, and method for producing water absorbing agent

By using randomly broken water-absorbing resin particles with surface crosslinking in the absorber and adjusting the proportion of specific compounds, the problem of discoloration of thin diapers in high temperature and humidity environments is solved, and the maintenance of water-absorbing properties and suppressing the discoloration rate is achieved.

CN115209987BActive Publication Date: 2025-04-08NIPPON SHOKUBAI CO LTD
View PDF 34 Cites 0 Cited by

Patent Information

Application Number
CN202180013277.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-14
Filing Date
2021-02-12
Publication Date
2025-04-08
Estimated Expiration
2041-02-12

AI Technical Summary

Technical Problem

The absorber of existing thin diapers is prone to discoloration in high temperature and humidity environments, affecting product performance and consumer satisfaction.

Method used

The water absorbing agent containing randomly broken water absorbing resin particles with surface crosslinking is used to control the moisture absorption rate and specific surface area by adjusting the ratio of α-hydroxy carboxylate and aminocarboxylic acid-based or phosphorus-based chelating agent, and to inhibit discoloration of the water absorbing agent.

Benefits of technology

While effectively maintaining the water-absorbing properties, it inhibits the increase in the discoloration speed of the water-absorbing agent and absorber, and improves the service life of the diaper and consumer satisfaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115209987B_ABST
    Figure CN115209987B_ABST
Patent Text Reader

Abstract

Provided is a water absorbent having a large specific surface area and a fast moisture absorption rate, good physical properties and a slow discoloration rate over time. Also provided is a low pulp ratio absorbent suitable for thin diapers having good physical properties and a slow discoloration rate over time. The absorbent comprises a hydrophilic substrate, and a water absorbent containing surface cross-linked random crushed water-absorbing resin particles, α-hydroxycarboxylic acid (salt) and aminocarboxylic acid chelating agent and / or phosphorus chelating agent. The plotted points obtained by plotting with the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbent as the X-axis and the amount y1 (mmol%) of the extracted aminocarboxylic acid chelating agent and / or phosphorus chelating agent as the Y-axis are within the range of satisfying a specific relationship between x1 and y1, and the moisture absorption rate of the water absorbent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120mg / g / hr or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an absorbent, a water absorbing agent, and a method for producing the water absorbing agent. Background Art

[0002] In recent years, sanitary products such as diapers for children, adults, and mild incontinence have shown a trend of becoming thinner, and the ratio of absorbent (or water-absorbing resin) in the absorbent of the sanitary products has been increasing. Generally speaking, the absorbent is formed by a mixture of absorbent and wood crushed pulp (and / or their composite). Wood crushed pulp is a white hydrophilic fiber with cellulose as the main body. In actual use, wood crushed pulp has the function of adjusting the humidity in the diaper before absorbing urine to suppress the wearer's stuffy feeling. In addition, when the diaper contains an absorbent, it also has the function of quickly absorbing the urine just discharged into the absorbent and diffusing the urine into the entire absorbent. However, with the thinning in recent years, the ratio of fiber materials such as pulp has decreased, and diapers with absorbents without pulp have appeared. As a result, the above-mentioned functions (humidity adjustment function, liquid capture function and diffusion function) previously undertaken by pulp in diapers and absorbents need to be replaced by absorbents. In response to this, multifunctional water-absorbing agents with excellent water-absorbing properties (e.g., absorption capacity under no pressure (CRC), absorption capacity under pressure (AAP), saline flow conductivity (SFC), absorption rate (Vortex and FSR)) have been developed. For example, a water-absorbing agent has been developed that improves Vortex and FSR by increasing the specific surface area while maintaining the CRC, AAP, and SFC performance of the water-absorbing agent. As a result, an absorbent containing such a water-absorbing agent has a humidity-control function and water-absorbing properties even when the pulp ratio is reduced due to thinning, and has been put into practical use.

[0003] On the other hand, depending on the storage and transportation conditions of the water absorbent used, the handling method of the absorbent containing the water absorbent, pulp, and adhesive, etc., and the storage conditions of the diaper containing the absorbent, the absorbent and the water absorbent may be exposed to a high temperature and high humidity environment for a long time, and thus the absorbent and the water absorbent may absorb moisture and change color over time. In particular, in an absorbent with a small pulp ratio, there are few white hydrophilic fibers, so for example, the discolored water absorbent affects the color of the absorbent, and the discolored absorbent can be seen from the front pad of the diaper, causing dissatisfaction among consumers. Therefore, as a method for suppressing such discoloration of the absorbent over time and reducing the discoloration speed of the water absorbent over time, for example, the water absorbents described in the following patent documents 1 to 5 have been proposed.

[0004] (Prior art literature)

[0005] (Patent Document)

[0006] Patent Document 1: WO2008 / 026772

[0007] Patent Document 2: WO2017 / 170604

[0008] Patent Document 3: WO2005 / 012369

[0009] Patent Document 4: Japanese Patent Application Publication No. 2000-327926

[0010] Patent Document 5: Japanese Patent Application Publication No. 2005-186016 Summary of the invention

[0011] (Problem to be solved by the invention)

[0012] However, the moisture absorption rate of the water-absorbing agent developed to improve the performance of the absorbent for thin diapers has also increased (although this has a good effect on the humidity control function of the absorbent), and there is a tendency for the color change rate of the water-absorbing agent to increase over time. For the water-absorbing agent used in diapers that are required to be thinner and have a reduced pulp ratio in the absorbent, it is still difficult to suppress the increase in the color change rate of the absorbent and the water-absorbing agent over time even if the conventional anti-discoloration technology is used.

[0013] Therefore, the subject of the present invention is to provide: an absorbent having a small pulp ratio and capable of well controlling the humidity in a diaper before absorbing urine, and not only maintaining its water absorption properties but also suppressing the increase in its color change rate over time; and a water-absorbing agent suitable for the absorbent.

[0014] In addition, other issues are to provide: a water absorbent having a large specific surface area and a fast moisture absorption rate, having good water absorption properties (CRC, AAP, SFC, absorption rate), and the increase in its color change rate over time is suppressed; and an absorbent with a small pulp ratio, having properties suitable for thin diapers (that is, having a humidity regulating function, a liquid capture function and a diffusion function in the diaper, and the water absorption properties are well maintained), and the increase in its color change rate over time is suppressed.

[0015] (Technical means to solve the problem)

[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the following absorbent and water-absorbing agent can solve the above-mentioned problems, thereby completing the present invention.

[0017] That is, one embodiment of the present invention includes the following aspects.

[0018] [A] An absorbent body comprising a hydrophilic substrate and a water absorbing agent, wherein:

[0019] The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles.

[0020] The plotted points obtained by plotting the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined in the following (a) or (b), and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120 mg / g / hr or more,

[0021] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0022] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0023] y1≥0…Formula (2);

[0024] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0025] y1≥0…Formula (2).

[0026] [B] An absorbent body comprising a hydrophilic substrate and a water absorbing agent, wherein:

[0027] The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles.

[0028] The plotted points are within the range defined in (a) or (b) below, with the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent x1 (mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent y1 (mmol%) as the Y-axis. The specific surface area of ​​the water absorbing agent is 32 m 2 / kg or more,

[0029] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0030] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0031] y1≥0…Formula (2);

[0032] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0033] y1≥0…Formula (2).

[0034] [C] The absorbent body according to [A] or [B], wherein a ratio of the mass of the water absorbing agent to the mass of the absorbent body is 75 mass % or more and 99 mass % or less.

[0035] [D] An absorbent article comprising the absorbent body according to any one of [A] to [C].

[0036] [E] A water-absorbing agent comprising surface-crosslinked randomly fragmented water-absorbing resin particles,

[0037] The plotted points obtained by plotting the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined in the following (a) or (b), and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120 mg / g / hr or more,

[0038] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0039] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0040] y1≥0…Formula (2);

[0041] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0042] y1≥0…Formula (2).

[0043] [F] A water-absorbing agent comprising surface-crosslinked randomly fragmented water-absorbing resin particles,

[0044] The plotted points are within the range defined in (a) or (b) below, with the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent x1 (mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent y1 (mmol%) as the Y-axis. The specific surface area of ​​the water absorbing agent is 32 m 2 / kg,

[0045] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0046] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0047] y1≥0…Formula (2);

[0048] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0049] y1≥0…Formula (2).

[0050] [G] The water-absorbing agent according to [E] or [F], wherein the change in WI value of the water-absorbing agent before and after the following color change test is 40 or less, and the WI value before the following color change test is 42 or more;

[0051] (The discoloration test is: exposing the water absorbing agent to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days).

[0052] [H] The water absorbing agent according to any one of [E] to [G], wherein the water absorbing agent satisfies the relationship of formula (3) and / or formula (4),

[0053] y2≥0.24x2+18…(3),

[0054] z2≥-10x2+306…(4),

[0055] In the formulas (3) and (4), x2 represents CRC, y2 represents AAP, z2 represents SFC, and x2 is a value greater than or equal to 26 and less than or equal to 32.

[0056] [I] A method for producing a water-absorbing agent, wherein the water-absorbing agent contains surface-crosslinked randomly fragmented water-absorbing resin particles,

[0057] The production method comprises a preparation step of preparing a monomer aqueous solution, wherein the monomer aqueous solution contains a monomer having acrylic acid (salt) as a main component and at least one polymerizable internal crosslinking agent.

[0058] In the preparation process,

[0059] An α-hydroxycarboxylic acid (salt), an aminocarboxylic acid chelating agent and / or a phosphorus chelating agent are added to the monomer aqueous solution respectively, so that: the plotted points obtained by plotting the amount x1 (mol%) of the α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined by the following (a) or (b); and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is adjusted to be 120 mg / g / hr or more,

[0060] (a) 0≤x1<0.19 and satisfy the following equations (1) and (2),

[0061] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0062] y1≥0…Formula (2);

[0063] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0064] y1≥0…Formula (2).

[0065] [J] A method for producing a water-absorbing agent, wherein the water-absorbing agent contains surface-crosslinked randomly fragmented water-absorbing resin particles,

[0066] The production method comprises a preparation step of preparing a monomer aqueous solution, wherein the monomer aqueous solution contains a monomer having acrylic acid (salt) as a main component and at least one polymerizable internal crosslinking agent.

[0067] In the preparation process,

[0068] An α-hydroxycarboxylic acid (salt), an aminocarboxylic acid chelating agent and / or a phosphorus chelating agent are added to the monomer aqueous solution respectively, so that: the plotted points obtained by plotting the amount x1 (mol%) of the α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X axis and the amount y1 (mmol%) of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent as the Y axis are within the range defined by the following (a) or (b); and the specific surface area of ​​the water absorbing agent is adjusted to 32 m 2 / kg or more,

[0069] (a) 0≤x1<0.19 and satisfy the following equations (1) and (2),

[0070] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0071] y1≥0…Formula (2);

[0072] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0073] y1≥0…Formula (2).

[0074] [K] The method for producing a water absorbing agent according to [I] or [J],

[0075] When the amount of α-hydroxycarboxylic acid (salt), aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from a water absorbing agent containing surface-crosslinked randomly fragmented water absorbing resin particles does not fall within the range defined in the following (a) or (b), the production method comprises the steps of adding α-hydroxycarboxylic acid (salt), aminocarboxylic acid chelating agent and / or phosphorus chelating agent to the water absorbing agent so that the amount falls within the range defined in the above (a) or (b),

[0076] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0077] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0078] y1≥0…Formula (2);

[0079] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0080] y1≥0…Formula (2).

[0081] [L] The method for producing a water absorbing agent according to any one of [I] to [K], comprising controlling the specific surface area of ​​the water absorbing agent before surface cross-linking to 32 m 2 / kg or more process.

[0082] (Effects of the Invention)

[0083] The present invention can provide an absorbent with a low pulp ratio suitable for thin diapers, which, when used as an absorbent with a low pulp ratio, can adjust the humidity in the diaper before absorbing urine to reduce the discomfort of the wearer, and has good water absorption properties and suppresses the increase in the color change rate over time. It can also provide a water absorbing agent with good water absorption properties (CRC, AAP, SFC, absorption rate) and suppresses the increase in the color change rate over time. BRIEF DESCRIPTION OF THE DRAWINGS

[0084] Figure 1 This is a graph showing the relationship between the amount of α-hydroxycarboxylic acid (salt) extracted and the amount of aminocarboxylic acid chelating agent or phosphorus chelating agent extracted in Examples and Comparative Examples of the present invention.

[0085] Figure 2 It is a graph which shows "CRC / AAP" and "CRC / SFC" of the water absorbing agent of the Example of this invention and a comparative example.

[0086] Figure 3 This is a schematic diagram showing a schematic structure of a constant temperature and humidity machine used when measuring moisture absorption rate in Examples and Comparative Examples of the present invention. DETAILED DESCRIPTION

[0087] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various schemes described below, and various changes can be made within the scope shown in the specification. The embodiments and embodiments obtained by appropriately combining the technical means respectively described in different embodiments and embodiments are also included in the technical scope of the present invention. In addition, all documents recorded in this specification are cited in this specification as reference documents. In this specification, if the description method "A to B" about the numerical range is recorded, the description means "above A and below B".

[0088] [1] Definition of terms

[0089] [1-1 Water absorbent

[0090] In this specification, "water absorbent" refers to a water-swellable, water-insoluble polymer gelling agent, which is generally in granular form. In addition, "water-swellable" means that the absorption capacity (CRC) under no pressure specified in NWSP241.0.R2 (15) is 5 g / g or more, and "water-insoluble" means that the soluble component (Ext) specified in NWSP270.0.R2 (15) is 50% by mass or less. In addition, "CRC" is the abbreviation of Centrifuge Retention Capacity, which refers to the absorption capacity of the water absorbent under no pressure.

[0091] The "water absorbent" contains a hydrophilic cross-linked polymer as a main component, and the hydrophilic cross-linked polymer is preferably formed by cross-linking and polymerizing an unsaturated monomer having a carboxyl group (hereinafter referred to as "unsaturated monomer containing a carboxyl group"). As mentioned above, the cross-linked polymer is generally granular, so the hydrophilic cross-linked polymer is a granular water-absorbing resin particle. However, it is not limited to the entire amount, that is, 100% by mass, of the cross-linked polymer (water-absorbing resin particles), and additives may also be contained within the range of satisfying the required performance of the CRC and Ext. The content of the water-absorbing resin particles relative to the water absorbent may be 90% by mass or more, 95% by mass or more, or 99% by mass or more.

[0092] Of all the monomers constituting the cross-linked polymer, for example, 1% by mass or more, 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 100% by mass may be an unsaturated monomer containing a carboxyl group.

[0093] In addition, the "water absorbent" sometimes refers to "a polymer that is only internally crosslinked (resin particles that are only internally crosslinked), that is, a resin particle (polymer) whose internal and surface crosslinking densities are substantially the same" or "resin particles (polymer) that are crosslinked both internally and on the surface, that is, a resin particle (polymer) whose surface crosslinking density is relatively high relative to the internal crosslinking density."

[0094] In principle, in this specification, no distinction is made between the "resin particles (polymer) crosslinked only internally" and the "resin particles (polymer) crosslinked both internally and on the surface", and both are referred to as "water absorbent". However, if it is necessary to clearly distinguish whether or not surface crosslinking is present, the "polymer (resin particles) crosslinked only internally" is referred to as "water absorbent before surface crosslinking" because it is in a state before surface crosslinking is performed, and the "polymer (resin particles) crosslinked both internally and on the surface" is referred to as "water absorbent after surface crosslinking" because it is in a state after surface crosslinking is performed. In addition, "before surface crosslinking" means "before adding a surface crosslinking agent" or "although a surface crosslinking agent has been added, the crosslinking reaction by heat treatment has not yet started".

[0095] The "water absorbing agent" may include components other than resins, such as additives, in addition to referring to only the resin component (water absorbing resin particles).

[0096] [1-2] Acrylic acid (salt) monomers, polyacrylic acid (salt) water absorbents

[0097] In the present specification, "acrylic acid (salt)" means acrylic acid and / or its salt, and "acrylic acid (salt)-based monomer" means acrylic acid (salt) contained therein in an amount of 50 mol% or more based on all monomers excluding the crosslinking agent.

[0098] In this specification, "polyacrylic acid (salt) water absorbing agent" refers to a polymer made of acrylic acid (salt). That is, "polyacrylic acid (salt) water absorbing agent" is a polymer containing a structural unit derived from acrylic acid (salt) and containing a graft component as an optional component.

[0099] Specifically, the polyacrylic acid (salt) water absorbent is an unsaturated polymer containing a carboxyl group as follows: the content of acrylic acid (salt) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more and preferably 100 mol% or less, and particularly preferably substantially 100 mol% relative to the portion of the monomers participating in the polymerization reaction excluding the internal crosslinking agent.

[0100] [1-3] "NWSP"

[0101] "NWSP" is the abbreviation of Non-Woven Standard Procedures-Edition 2015, which is a method for evaluating nonwoven fabrics and their products that was jointly developed by EDANA (European Disposables and Nonwovens Associations) and INDA (Association of the Nonwoven Fabrics Industry) and is adopted uniformly in Europe and the United States. In addition, NWSP also shows the standard measurement method for water-absorbent resins. In this manual, the physical properties of water-absorbent resins are measured in accordance with the original NWSP (2015).

[0102] Unless otherwise specified in the present specification, the methods for measuring various physical properties of the water absorbing agent shall be carried out according to the measuring methods of the following examples.

[0103] [1-4] Others

[0104] In the present specification, "a certain acid (salt)" means "a certain acid and / or its salt", and "(meth)acryl" means "acryl and / or methacryl".

[0105] [2] Water absorbent

[0106] The water-absorbing agent according to one embodiment of the present invention is a surface-crosslinked randomly fragmented water-absorbing agent, which has a moisture absorption rate of 120 mg / g / hr or more when left at rest under an environment of a temperature of 40±1° C. and a relative humidity of 75±1% RH, and the plotted points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted therefrom (x1 mol%) as the X-axis and the amount of aminocarboxylic acid-based chelating agent and / or phosphorus-based chelating agent extracted therefrom (y1 mmol%) as the Y-axis are within the range defined by formula (A) and formula (B).

[0107] y1≥0…Formula (A)

[0108] 0≤x1≤0.33…Formula (B)

[0109] But this does not include the following range: y1≤28.7x1 2 -11.1x1+1.07and 0≤x1<0.19.

[0110] A water absorbing agent according to one embodiment of the present invention comprises surface-crosslinked randomly fragmented water absorbing resin particles, wherein:

[0111] The plotted points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent (y1 mmol%) as the Y-axis are within the range defined by the following (a) or (b), and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120 mg / g / hr or more.

[0112] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0113] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0114] y1≥0…Formula (2).

[0115] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0116] y1≥0…Formula (2).

[0117] In addition, the water absorbing agent according to another embodiment of the present invention is a surface cross-linked randomly fragmented water absorbing agent having a specific surface area of ​​32 m 2 / kg or more, and the plotting points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted therefrom (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted therefrom (y1 mmol%) as the Y-axis are within the range defined by formula (A) and formula (B).

[0118] y1≥0…Formula (A)

[0119] 0≤x1≤0.33…Formula (B)

[0120] But this does not include the following range: y1≤28.7x1 2 -11.1x1+1.07and 0≤x1<0.19.

[0121] A water absorbing agent according to one embodiment of the present invention comprises surface-crosslinked randomly fragmented water absorbing resin particles, wherein:

[0122] The plotted points are within the range defined in (a) or (b) below, with the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent (y1 mmol%) as the Y-axis. The specific surface area of ​​the water absorbing agent is 32 m 2 / kg or more.

[0123] (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2),

[0124] y1>28.7x1 2 -11.1x1+1.07…Formula (1),

[0125] y1≥0…Formula (2).

[0126] (b) 0.19≤x1≤0.33 and satisfies the following formula (2),

[0127] y1≥0…Formula (2).

[0128] In formula (A), the upper limit of y1 is not limited, but may be, for example, 10.00 mmol%, 5.00 mmol%, 3.00 mmol%, or 2.00 mmol%.

[0129] In formula (2), the upper limit of y1 is not limited, but may be, for example, 10.00 mmol%, 5.00 mmol%, 3.00 mmol%, or 2.00 mmol%.

[0130] One of the main purposes of the present invention is to find a range that suppresses the increase in the discoloration rate over time while maintaining good water absorption properties, and the range shown in the combination of x1 and y1 is the empirical rule range derived for this purpose.

[0131] The surface cross-linked water absorbent of one embodiment of the present invention has a large specific surface area and a fast moisture absorption rate. When used in an absorbent with a small pulp ratio, it can adjust the humidity in the diaper before absorbing urine, thereby reducing the discomfort of the wearer, and while having good physical properties, the discoloration rate over time is also reduced. Therefore, the moisture absorption rate of the surface cross-linked water absorbent of one embodiment of the present invention can be 120 mg / g / h or more, 135 mg / g / h or more, or 150 mg / g / h or more. The upper limit of the moisture absorption rate of the surface cross-linked water absorbent of one embodiment of the present invention is not particularly limited, but the moisture absorption rate can be, for example, 190 mg / g / h or less, 175 mg / g / h or less, or 160 mg / g / h or less. If the moisture absorption rate is 120 mg / g / h or more, when the water absorbent is used in an absorbent with a small pulp ratio, the water absorbent can adjust the humidity in the diaper before absorbing urine, thereby reducing the discomfort of the wearer.

[0132] In addition, the specific surface area of ​​the surface cross-linked water absorbing agent according to another embodiment of the present invention may be 32 m 2 / kg or more, 36m 2 / kg or more, 40m 2 / kg or more, 44m 2 / kg or more, 48m 2 / kg or more, 52m 2 / kg or more, 56m 2 / kg or more, or 60m 2 The upper limit of the specific surface area of ​​the surface-crosslinked water-absorbing agent of one embodiment of the present invention is not particularly limited, but the specific surface area may be, for example, 100 m 2 / kg or less, 80m 2 / kg or less, or 70m 2 / kg or less.

[0133] Regarding the surface cross-linked water absorbent of one embodiment of the present invention, although α-hydroxycarboxylic acid (salt) may not be added if the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent is sufficient and within the range defined by the formula (A), basically, the amount of α-hydroxycarboxylic acid (salt) extracted relative to the amount of carboxyl-containing unsaturated monomer contained in the water absorbent exceeds 0 mol% (or is 0 mmol% or more), preferably 0.03 mol% or more, more preferably 0.06 mol% or more, and preferably 0.33 mol% or less, more preferably 0.30 mol% or less, and further preferably 0.27 mol% or less. By this scheme, it is possible to better maintain good physical properties and reduce the speed of discoloration over time.

[0134] The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent can be measured by, for example, extracting from the water absorbing agent using a 0.9 mass % sodium chloride aqueous solution and quantifying the amount of α-hydroxycarboxylic acid (salt) extracted in the 0.9 mass % sodium chloride aqueous solution. More specifically, the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent can be measured by the method described in the Examples below.

[0135] Regarding the surface cross-linked water absorbent of one embodiment of the present invention, although if the amount of α-hydroxycarboxylic acid (salt) is sufficient and within the range defined by the formula (B), aminocarboxylic acid chelating agent and / or phosphorus chelating agent are sometimes not added, but basically, relative to the amount of the unsaturated monomer containing carboxyl group contained in the water absorbent, the amount of the extracted aminocarboxylic acid chelating agent and / or phosphorus chelating agent exceeds 0mmol% (or is 0mmol% or more), preferably 0.05mmol% or more, more preferably 0.10mmol% or more, and preferably 10mmol% or less, more preferably 7.5mmol% or less, and further preferably 5.0mmol% or less. Even if the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is increased, it will not have an adverse effect on physical properties and discoloration speed, but if it exceeds 10mmol%, it is not economical in cost, so it is not preferred. Through this scheme, it is possible to better maintain good physical properties and reduce the discoloration speed over time.

[0136] The amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent can be measured, for example, by the following method: extracting the water absorbing agent with a 0.9 mass % sodium chloride aqueous solution, and quantifying the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted and present in the 0.9 mass % sodium chloride aqueous solution, thereby measuring the amount. More specifically, the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent can be measured by the method described in the embodiments described later. In order to suppress the cost of the product, it is preferred that even when the amount of α-hydroxycarboxylic acid (salt) extracted is small, it is better to maintain good physical properties and reduce the discoloration speed over time. In this embodiment, when the extraction amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent is greater than 0.40 mmol% and less than 1.20 mmol%, and the extraction amount of α-hydroxycarboxylic acid (salt) is greater than 0.06 mol% and less than 0.15 mol%, it is possible to better maintain good physical properties, reduce the speed of discoloration over time, and suppress the cost of the product.

[0137] The WI value change of the surface cross-linked water absorbent of one embodiment of the present invention before and after the discoloration (discoloration under the discoloration test) described below with the passage of time is preferably 40 or less, more preferably 39.5 or less, and further preferably 39 or less. When the change is within this range, the surface cross-linked water absorbent of one embodiment of the present invention is practical regardless of the numerical difference. In addition, the WI value of the surface cross-linked water absorbent of one embodiment of the present invention before the discoloration test described below is preferably 42 or more, more preferably 46 or more, and further preferably 50 or more. The above-mentioned discoloration test refers to a test in which the water absorbent is exposed to an environment of a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1RH% for 7 days, more specifically, the test described in the examples described later. Through this scheme, it is possible to better maintain good physical properties while reducing the discoloration rate over time. The WI change is shown in the following formula.

[0138] ΔWI (change amount) = |WI (after the color change test) - WI (before the color change test) | ... (formula).

[0139] The surface cross-linked water-absorbing agent of one embodiment of the present invention preferably satisfies the relationship of the following formula (3) and / or formula (4). The surface cross-linked water-absorbing agent of one embodiment of the present invention more preferably satisfies the relationship of the following formula (3) and formula (4). By this scheme, it is possible to better maintain good physical properties and reduce the speed of discoloration over time.

[0140] y2≥0.24x2+18…(3)

[0141] z2≥-10x2+306…(4)

[0142] Here, in formula (3) and formula (4), x2 represents CRC, y2 represents AAP, z2 represents SFC, and x2 is preferably 26 or more, more preferably 26.5 or more, and more preferably 27.0 or more, and preferably 32.0 or less, more preferably 31.0 or less, and more preferably 30.5 or less. y2 satisfies formula (B) and is preferably 24.5 or more, more preferably 25.0 or more, more preferably 25.5 or more, and most preferably 26.0 or more. The upper limit value of y2 is not particularly limited, but y2 is generally 30 or less. In addition, z2 satisfies formula (3) and is 0 or more, preferably 10 or more, more preferably 15 or more, and more preferably 20 or more. The upper limit value of z2 is not particularly limited, but if x2 is within the above range, z2 is generally 80 or less.

[0143] Hereinafter, an example of a method for producing the water absorbing agent will be described.

[0144] [3] Method for producing water-absorbing agent

[0145] [3-1] Preparation process of monomer aqueous solution

[0146] This step is a step of preparing a monomer aqueous solution containing a monomer mainly composed of acrylic acid (salt) and at least one polymerizable internal crosslinking agent. Although a monomer slurry may also be used, for convenience, the monomer aqueous solution is described in this specification.

[0147] (monomer)

[0148] As the monomer used in the present invention, for example, anionic unsaturated monomers and / or salts thereof such as acrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(methyl)acrylamide-2-methylpropane sulfonic acid, 2-(methyl)acryloylethane sulfonic acid, 2-(methyl)acryloylpropane sulfonic acid, and 2-hydroxyethyl (methyl)acryloyl phosphate can be cited; unsaturated monomers containing mercapto groups; phenolic unsaturated monomers containing hydroxyl groups; unsaturated monomers containing amide groups such as (methyl)acrylamide, N-ethyl (methyl)acrylamide, and N,N-dimethyl (methyl)acrylamide; unsaturated monomers containing amino groups such as N,N-dimethylaminoethyl (methyl)acrylic acid, N,N-dimethylaminopropyl (methyl)acrylamide, and the like. The monomer includes water-soluble or hydrophobic unsaturated monomers. Among these, acrylic acid (salt) is preferred. In addition, acrylic acid (salt) may be used in combination with other monomers. In this case, the amount of acrylic acid (salt) used is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably substantially 100 mol% relative to all monomers except the crosslinking agent.

[0149] (Neutralization using alkaline compounds)

[0150] In the present invention, when acrylic acid (salt) monomers are used, acrylic acid is preferably partially neutralized with a basic compound. That is, in the present invention, a water-absorbing resin in which the acid groups of polyacrylic acid are partially neutralized is preferred.

[0151] As the alkaline compound, for example, carbonates and bicarbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, etc. can be cited. Among them, from the viewpoint of the water absorption performance of the water absorbent, a strongly alkaline compound can be selected. Therefore, hydroxides of alkali metals such as sodium, potassium, and lithium are preferred, and sodium hydroxide is more preferred. In addition, from the viewpoint of operability, the alkaline compound is preferably in the form of an aqueous solution. Here, generally commercially available sodium hydroxide contains heavy metals such as zinc, lead, and iron at the ppm level (mass basis), so strictly speaking, it can be said to be a composition. In the present invention, the composition is also included in the scope of the alkaline compound.

[0152] The neutralization may be performed before, during or after the polymerization, and may be performed at multiple times or a plurality of times. In addition, continuous neutralization is preferred from the viewpoint of production efficiency of the water absorbing agent.

[0153] In the present invention, when acrylic acid (salt) is used, the neutralization rate of acrylic acid (salt) relative to the acid group of the monomer is preferably 10 mol% or more, more preferably 40 mol% or more, further preferably 50 mol% or more, particularly preferably 60 mol% or more, and preferably 90 mol% or less, more preferably 85 mol% or less, further preferably 80 mol% or less, particularly preferably 75 mol% or less. When the neutralization rate is within this range, the decrease in the water absorption performance of the water absorbent can be suppressed. The above-mentioned neutralization rate requirements are also applicable to the aforementioned neutralization before, during, and after polymerization. In addition, it is also applicable to the water absorbent.

[0154] (Internal crosslinking agent)

[0155] In the preferred production method of the present invention, an internal crosslinking agent is used. Examples of the internal crosslinking agent include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, glycerol acrylate methacrylate, ethoxy-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerol, pentaerythritol, ethylenediamine, polyethyleneimine, glycidyl(meth)acrylate, and the like. At least one internal cross-linking agent is selected from these internal cross-linking agents in consideration of reactivity and the like.

[0156] In the present invention, from the viewpoint of the water absorption performance of the water absorbent, it is preferred to select an internal crosslinking agent having two or more polymerizable unsaturated groups, and it is more preferred to select an internal crosslinking agent having a (poly) alkylene glycol structural unit and having two or more polymerizable unsaturated groups. As the polymerizable unsaturated group, specifically, allyl group and (meth) acrylate group can be cited. Among them, (meth) acrylate group is preferred. In addition, regarding the internal crosslinking agent having the (poly) alkylene glycol structural unit and having two or more polymerizable unsaturated groups, polyethylene glycol di(meth) acrylate can be cited. Regarding the number of alkylene glycol structural units (hereinafter, denoted as "N"), it is preferably 1 or more, more preferably 2 or more, further preferably 4 or more, and particularly preferably 6 or more, and is preferably 100 or less, more preferably 50 or less, further preferably 20 or less, and particularly preferably 10 or less.

[0157] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more, more preferably 0.001 mol% or more, and further preferably 0.01 mol% or more, and preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 1 mol% or less, relative to the monomers other than the internal crosslinking agent. When the amount is within this range, a water-absorbing agent having the desired water-absorbing performance can be obtained. On the other hand, when the amount is outside this range, an increase in water-soluble components and a decrease in absorption rate may occur as the gel strength decreases.

[0158] In the present invention, the internal crosslinking agent may be added at a time that allows the polymer to be uniformly crosslinked, and examples thereof include a method of adding the internal crosslinking agent to the aqueous monomer solution before polymerization, during polymerization, or to the hydrogel after polymerization. Among them, a method of adding a predetermined amount of the internal crosslinking agent to the aqueous monomer solution in advance is preferred.

[0159] (Substances added to the aqueous monomer solution)

[0160] In the present invention, from the viewpoint of improving the physical properties of the water absorbing agent, the following substances may be added to the monomer aqueous solution at any one or more stages during the preparation of the monomer aqueous solution, during the polymerization reaction and the crosslinking reaction, or after the polymerization reaction and the crosslinking reaction.

[0161] Specific examples of such substances include hydrophilic polymers such as α-hydroxycarboxylic acid (salt) compounds, starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol (PVA), polyacrylic acid (salt), and cross-linked products of polyacrylic acid (salt); and compounds such as carbonates, azo compounds, various bubble-generating foaming agents, surfactants, aminocarboxylic acid chelating agents and / or phosphorus chelating agents, and chain transfer agents.

[0162] Examples of the α-hydroxycarboxylic acid (salt) compound include malic acid (salt), lactic acid (salt), glycolic acid (salt), tartaric acid (salt), citric acid (salt), and mandelic acid (salt).

[0163] If the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent is sufficient, the α-hydroxycarboxylic acid (salt) compound may not be added, but basically, the amount of the α-hydroxycarboxylic acid (salt) compound added is preferably 0.41 mol% or less, more preferably 0.37 mol% or less, and further preferably 0.33 mol% or less, relative to the unsaturated monomer containing a carboxyl group contained in the water absorbent, and may be 0 mmol%, preferably more than 0 mol%, more preferably 0.04 mol% or more, further preferably 0.06 mol% or more, and particularly preferably 0.08 mol% or more. If the amount of the α-hydroxycarboxylic acid (salt) compound added exceeds this range, the water absorption properties (especially AAP and SFC) of the water absorbent will decrease, and the balance between the effect of suppressing discoloration over time and the absorption properties will deteriorate, so it is not preferred.

[0164] More specifically, the aminocarboxylic acid chelating agent includes Japanese Patent Application Laid-Open No. 11-060975, International Publication No. 2007 / 004529, International Publication No. 2011 / 126079, International Publication No. 2012 / 023433, Japanese Patent Application Laid-Open No. 2009-509722, Japanese Patent Application Laid-Open No. 2005-097519, Chelating agents disclosed in Japanese Unexamined Patent Publication No. 2011-074401, Japanese Unexamined Patent Publication No. 2013-076073, Japanese Unexamined Patent Publication No. 2013-213083, Japanese Unexamined Patent Publication No. 59-105448, Japanese Unexamined Patent Publication No. 60-158861, Japanese Unexamined Patent Publication No. 11-241030, Japanese Unexamined Patent Publication No. 2-41155, etc.

[0165] As the phosphorus-based chelating agent used in the present invention, it is preferred to use an organic aminophosphoric acid having an amino group, a water-soluble organic aminophosphoric acid, and further a water-soluble non-polymer organic aminophosphoric acid. In the average organic aminophosphoric acid, the number of amino groups is preferably 1 or more, more preferably 2 or more, and the number of phosphate groups is preferably 1 or more, more preferably 2 or more, and particularly preferably 3 or more. The upper limits of the number of amino groups and the number of phosphate groups are generally 100 or less, more preferably 10 or less, and particularly preferably 5 or less. The so-called water solubility in the present invention means that the compound can dissolve more than 0.1 g, more preferably 1 g or more, and particularly preferably 5 g or more relative to 100 g of water at 25°C. In addition, its molecular weight is generally in the range of 50 to 5000, preferably in the range of 100 to 1000, and further preferably in the range of 200 to 500.

[0166] As the phosphorus chelating agent used, for example, ethylenediamine-N, N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), nitriloacetic acid-di(methylene phosphinic acid), nitrilodiacetic acid-(methylene phosphinic acid), nitriloacetic acid-β-propionic acid-methylene phosphinic acid, nitrilotri(methylene phosphinic acid), cyclohexanediaminetetra(methylene phosphinic acid), ethylenediamine-N, N'-diacetic acid-N, N'-di(methylene phosphinic acid), ethylenediamine-N, N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), polymethylenediaminetetra(methylene phosphinic acid), diethylenetriaminepenta(methylene phosphinic acid), 1-hydroxyethylenediphosphinic acid, and their salts. The most preferred phosphorus chelating agent in the present invention is ethylenediamine-tetra(methylene phosphinic acid) or its salt. As preferred salts, alkali metal salts, ammonium salts, and amine salts such as sodium salts and potassium salts can be cited. In addition, as the salt, a sodium salt and a potassium salt are particularly preferred.

[0167] If the amount of α-hydroxycarboxylic acid (salt) is sufficient, the aminocarboxylic acid chelating agent and / or phosphorus chelating agent may not be added sometimes, but basically, the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is preferably 20 mmol% or less, more preferably 18 mmol% or less, and further preferably 16 mmol% or less, particularly preferably 14 mmol%, relative to the unsaturated monomer containing a carboxyl group contained in the water absorbent, and may be 0 mmol%, preferably more than 0 mmol%, more preferably 0.4 mmol% or more, and further preferably 0.8 mmol% or more. If the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added exceeds the above range, it is not only uneconomical, but also the color of the chelating agent used will make the color tone of the water absorbent worse, so it is not preferred.

[0168] α-hydroxycarboxylic acid (salt), aminocarboxylic acid chelating agent and / or phosphorus chelating agent can be added in any process described later, but if these additives are unevenly present in the water absorbent, particles that change color over time and particles that do not change color will appear mixedly, so the discoloration inhibition effect is likely to be uneven depending on the different material collection positions or manufacturing batches in the manufacturing process of the absorbent and the absorbent article. Therefore, the timing of the addition process of α-hydroxycarboxylic acid (salt), aminocarboxylic acid chelating agent and / or phosphorus chelating agent is preferably in the surface cross-linking process and before, more preferably in the gel crushing process and before, and further preferably in the polymerization process and before, and most preferably in the adjustment process of the monomer aqueous solution. Compared with the water absorbent added after the process (for example, added after the surface cross-linking agent process), the water absorbent added in the process (for example, added in the polymerization process or before) has higher performance and can achieve stable physical properties.

[0169] (Concentration of monomer component)

[0170] The above-mentioned substances and components (hereinafter referred to as "monomer components") are selected according to the purpose, and their respective amounts are determined so as to satisfy the above-mentioned ranges, and they are mixed with each other to prepare a monomer aqueous solution. In the present invention, the monomer may be in the form of an aqueous solution or a mixed solution of water and a hydrophilic solvent.

[0171] In addition, from the viewpoint of the physical properties of the water-absorbing agent, the total concentration of the monomer components is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less. The concentration of the monomer components is calculated by the following formula (A).

[0172] Concentration of monomer component (mass %) = [(mass of monomer component) / (mass of monomer aqueous solution)] × 100 ... Formula (A)

[0173] In the above formula (A), "the mass of the monomer aqueous solution" does not include the mass of the graft component, the mass of the water absorbing agent, and the mass of the hydrophobic organic solvent used in the case of reverse phase suspension polymerization.

[0174] [3-2] Polymerization process

[0175] In this step, the monomer aqueous solution is polymerized to obtain a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel"). Preferably, the step is to polymerize the monomer aqueous solution obtained in the monomer aqueous solution preparation step to obtain a hydrogel, wherein the monomer aqueous solution contains a carboxyl group-containing unsaturated monomer containing acrylic acid (salt) as a main component and at least one polymerizable internal crosslinking agent.

[0176] (Polymerization initiator)

[0177] The polymerization initiator used in the present invention can be selected from one or more polymerization initiators commonly used in the production of water absorbing agents, depending on the type of polymerization monomers and polymerization conditions, etc. Examples of the polymerization initiator include thermal decomposition initiators and photodecomposition initiators.

[0178] Examples of the thermal decomposition initiator include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides such as hydrogen peroxide, tert-butyl peroxide, and methyl ethyl ketone peroxide; and azo compounds such as azonitrile compounds, azo amidine compounds, cyclic azo amidine compounds, azoamide compounds, alkylazo compounds, 2,2'-azobis(2-amidinopropane) dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride.

[0179] Examples of the photodegradable initiator include benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, and azo compounds.

[0180] Among these, persulfate is preferred in view of the cost and the ability to suppress the occurrence of residual monomers. In addition, a reducing agent that promotes the decomposition of the oxidative polymerization initiator such as the persulfate or peroxide can also be used in combination, so as to obtain a redox system initiator by combining the oxidative polymerization initiator and the reducing agent. As the reducing agent, for example, (heavy) sulfurous acid (salts) such as sodium sulfite and sodium bisulfite, L-ascorbic acid (salts), reducing metals (salts) such as ferrous salts, amines, etc. can be cited.

[0181] The amount of the polymerization initiator used is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, and preferably 1 mol% or less, more preferably 0.5 mol% or less, and further preferably 0.1 mol% or less, relative to the monomers other than the internal crosslinking agent. In addition, the amount of the reducing agent used is preferably 0.0001 mol% or more, more preferably 0.0005 mol% or more, and preferably 0.02 mol% or less, more preferably 0.015 mol% or less, relative to the monomers other than the internal crosslinking agent. When the amount used is within this range, a water absorbing agent having the desired water absorbing performance can be obtained.

[0182] In the present invention, the polymerization reaction may be initiated by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays. In addition, irradiation with active energy rays and the polymerization initiator may be used in combination.

[0183] (g) Inhibitor

[0184] During the polymerization, it is preferred to contain a polymerization inhibitor. Examples of the polymerization inhibitor include N-oxyl radical compounds, manganese compounds, and substituted phenol compounds listed in International Publication No. 2008 / 096713, preferably substituted phenols, and particularly preferably methoxyphenols.

[0185] As the methoxyphenols that can be preferably used, specifically, o-, m-, p-methoxyphenol (o, m, p-methoxyphenol), and methoxyphenols having one or more methyl, tert-butyl, hydroxyl, etc. substituents can be exemplified. The methoxyphenols that are particularly preferably used in the present invention are p-methoxyphenol. The content of the methoxyphenols may be 5 to 200 ppm, preferably 5 to 160 ppm, more preferably 10 to 160 ppm, more preferably 10 to 100 ppm, more preferably 10 to 80 ppm, and most preferably 10 to 70 ppm.

[0186] If the content of p-methoxyphenol exceeds 200ppm, the obtained water-absorbent resin may be discolored (yellowing / yellowing). If the content of p-methoxyphenol is less than 10ppm, especially less than 5ppm, that is, if p-methoxyphenol as a polymerization inhibitor is removed by purification treatment such as distillation, there is not only a risk of accidental polymerization before the start of polymerization, but also the polymerization rate may unexpectedly slow down, which is not preferred. If the content of p-methoxyphenol is even lower, the light resistance of the swollen gel of the obtained water-absorbent resin is poor, which is not preferred. Generally speaking, the swollen gel of the water-absorbent resin is deteriorated by light, but in the present invention, it was found that the light resistance can be improved by using p-methoxyphenol.

[0187] (h) Fe content and other impurities

[0188] The monomer in this specification preferably contains iron, or the iron content is zero. Relative to the monomer, the iron content (Fe) is less than 2ppm, preferably less than 1.5ppm, more preferably less than 1.0pm, more preferably less than 0.5ppm, and particularly preferably less than 0.3ppm. If there is more iron, the polymerization rate will decrease, resulting in an increase in residual monomers, thereby generating odor, and the resulting water-absorbing resin will have problems of discoloration and deterioration, so it is not preferred. Iron is mainly contained in the alkali used for neutralization, especially caustic soda, sodium (bicarbonate), so the iron content can be controlled by controlling the purity of caustic soda, etc. Considering the purification cost of alkali (especially caustic soda), the lower limit of the iron content (Fe) is 0.001ppm, and 0.01ppm is sufficient.

[0189] For example, if NaOH contains 5 ppm of Fe, then according to "acrylic acid (molecular weight 72) + NaOH (molecular weight 40) × 0.75 = 75 mol% neutralized sodium acrylate (molecular weight 88.5)", the amount of iron (Fe) in the 75 mol% neutralized sodium acrylate is 5 ppm × (40 × 0.75 / 88.5) = 1.7 ppm. The amount of iron in the alkali and in the water-absorbent resin can be quantified by the ICP emission spectroscopic analysis method described in JIS K1200-6, for example. As a reference for the quantitative method, International Publication No. 2008 / 090961 can be referred to.

[0190] In addition, among the six impurities of protoanemonin, allyl acrylate, allyl alcohol, aldehyde component (especially furfural), maleic acid, and benzoic acid in acrylic acid, one or more, or two or more, or three or more, or four or more, or five or more, or all six are 0 to 20 ppm each. Preferably, each is 0 to 10 ppm, more preferably, each is 0 to 5 ppm, further preferably, each is 0 to 3 ppm, particularly preferably, each is 0 to 1 ppm, and most preferably, each is ND (below the detection limit). In addition, the total amount of these protoanemonin, allyl acrylate, allyl alcohol, aldehyde component, maleic acid, and benzoic acid (relative to the weight of acrylic acid) is preferably 100 ppm or less, more preferably, 0 to 20 ppm, and further preferably, 0 to 10 ppm. As a preferred control method for controlling these trace components and propionic acid, acrylic acid derived from non-fossil raw materials can be used.

[0191] If the impurities are too much, the residual monomers and soluble components of the water-absorbent resin will increase, or discoloration will occur. Similarly, from the viewpoint of residual monomers, the water content in acrylic acid is preferably 20% by weight or less, more preferably 1% by weight or less, further preferably 0.5% by weight or less, and particularly preferably 0.2% by weight or less. That is, it is more preferable to use acrylic acid (water content of 0.2% by weight or less) in the monomer preparation compared to an acrylic acid aqueous solution (e.g., a commercially available 80% by weight aqueous solution).

[0192] (Aggregate form)

[0193] As the polymerization form applicable to the present invention, aqueous solution polymerization, reversed suspension polymerization, spray polymerization, droplet polymerization, large-scale polymerization, precipitation polymerization, etc. can be enumerated. Wherein, from the viewpoint of the easy controllability of polymerization and the water absorption performance of water absorbing agent, aqueous solution polymerization or reversed suspension polymerization is preferably selected, aqueous solution polymerization is more preferably selected, and continuous aqueous solution polymerization is further preferably selected. About reversed suspension polymerization, there are records in International Publication No. 2007 / 004529, International Publication No. 2012 / 023433, etc. In addition, continuous aqueous solution polymerization can manufacture water absorbing agent with higher productivity, and can enumerate the continuous belt polymerization recorded in U.S. Patent No. 4893999, U.S. Patent No. 6906159, U.S. Patent No. 7091253, U.S. Patent No. 7741400, U.S. Patent No. 8519212, Japanese Patent Publication No. 2005-36100 Gazette, etc. and the kneader continuous polymerization recorded in U.S. Patent No. 6987151, etc.

[0194] Preferred forms of the continuous aqueous solution polymerization include high-temperature start polymerization, high-concentration polymerization, foaming polymerization, and the like. The "high-temperature start polymerization" refers to the following polymerization form: the temperature of the monomer aqueous solution at the start of the polymerization is preferably 35°C or above, more preferably 40°C or above, further preferably 45°C or above, and especially preferably 50°C or above, and is preferably below the boiling point of the monomer aqueous solution. In addition, "high-concentration polymerization" refers to the following polymerization form: the monomer concentration at the start of the polymerization is preferably 30% by mass or above, more preferably 35% by mass or above, further preferably 40% by mass or above, and especially preferably 45% by mass or above, and is preferably below the saturation concentration of the monomer aqueous solution. "Foaming polymerization" refers to the following polymerization form: the monomer aqueous solution containing a foaming agent or bubbles is polymerized. These polymerization forms can be implemented separately, or two or more types can be implemented in combination.

[0195] Regarding the method for dispersing bubbles during the foaming polymerization, there are the following methods: a method of reducing the solubility of the gas dissolved in the monomer aqueous solution to disperse the gas as bubbles, a method of introducing gas from the outside to disperse the gas as bubbles, a method of adding a foaming agent to the monomer aqueous solution to foam it, etc. In addition, these dispersion methods can be appropriately used in combination according to the target physical properties of the water absorbent.

[0196] When the gas is introduced from the outside, specific examples of the gas include oxygen, air, nitrogen, carbon dioxide, ozone, and mixed gases thereof. From the viewpoint of polymerizability and cost, inert gases such as nitrogen and carbon dioxide are preferably used, and nitrogen is more preferably used.

[0197] Usable foaming agents include azo compounds, organic or inorganic carbonate solutions, dispersions, and powders with a particle size of 0.1 μm to 1000 μm. Among them, inorganic carbonates are preferred, and specifically, carbonates and bicarbonates such as sodium carbonate, ammonium carbonate, and magnesium carbonate can be used.

[0198] The foamed hydrogel obtained by foaming polymerization is subjected to gel crushing, which makes it easier to dry. In addition, making the water absorbent foamable can increase the water absorption rate of the water absorbent. "Foaming" means that under an electron microscope, it can be observed that the surface of the water absorbent particles has holes and crater-like depressions such as crater-like depressions formed by the loss of a part of a sphere. The holes and depressions can be judged by confirming whether the diameter is 1 μm or more and 100 μm or less. The number of holes and depressions on each water absorbent particle is preferably 1 or more, more preferably 3 or more, and particularly preferably 10 or more, and preferably 10,000 or less, more preferably 1,000 or less, and particularly preferably 100 or less. For example, when observing 100 particles classified in the range of 600 μm to 300 μm, the particles that meet the above items are preferably 5 or more, more preferably 10 or more, and more preferably 20 or more. These can be controlled by the foaming polymerization.

[0199] [3-3] Gel crushing process

[0200] This step is a step of pulverizing the hydrogel, which is performed in the middle of the polymerization step and / or after the polymerization step. Specifically, the hydrogel may be pulverized in the polymerization step or after the polymerization step. That is, this step is a step of obtaining a granular hydrogel (hereinafter referred to as "granular hydrogel") by gel pulverizing the hydrogel. In order to distinguish it from the "pulverization" in the pulverizing step described later, this step is referred to as "gel pulverization".

[0201] The gel pulverization is to adjust the hydrogel to a predetermined size using a kneader, a screw-type extruder such as a meat grinder, or a gel pulverizer such as a cutter mill.

[0202] When the hydrogel is subjected to gel grinding, warm water is preferably added to the gel grinder. Adding warm water is preferred because it is possible to obtain a granular hydrogel with reduced stickiness and good air permeability, which facilitates drying. The temperature of the warm water is preferably 40°C or higher, more preferably 50°C or higher, and still more preferably 60°C or higher, and preferably 100°C or lower.

[0203] Regarding the implementation method and operating conditions of gel grinding, the contents described in the International Publication No. 2011 / 126079 are preferably applicable to the present invention. If the polymerization form is kneader polymerization, this is equivalent to the polymerization step and the gel grinding step being carried out simultaneously. In addition, in the present invention, a water absorbent in a randomly crushed state can be obtained through the gel grinding step.

[0204] From the viewpoint of easy drying and the physical properties of the obtained water-absorbing agent, the particle size of the granular hydrogel granulated by the gel pulverization step is preferably in the range of 0.1 mm or more and 10 mm or less. In addition, the mass average particle size (D50) of the granular hydrogel is preferably 0.1 mm or more and preferably 5 mm or less, and more preferably 2 mm or less. If the mass average particle size (D50) of the granular hydrogel deviates from the above range, drying may be insufficient. In the present invention, the mass average particle size of the hydrogel provided to the drying step is preferably within the above range, and more preferably both the particle size and the mass average particle size satisfy the above range.

[0205] In order to increase the specific surface area of ​​the water absorbent, it is preferable to use the gel grinding method described in the pamphlet of International Publication No. 2011 / 126079. In addition, the gel grinding method can be used in combination with the above-mentioned foaming polymerization.

[0206] In order to dry uniformly and efficiently, the water content of the particulate hydrogel is preferably 30% by mass or more, more preferably 45% by mass or more, and is preferably 70% by mass or less, more preferably 55% by mass or less.

[0207] [3-4] Drying process

[0208] This process is a process of drying the crushed hydrogel, specifically, a process of drying the granular hydrogel to a desired solid content, thereby obtaining a dry polymer. The solid content is the value obtained by subtracting the water content from 100% by mass of the gel, and is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, particularly preferably 92% by mass or more, and preferably 99% by mass or less, further preferably 98% by mass or less, and particularly preferably 97% by mass or less. If the solid content of the dry polymer is within the above range, crushing, classification, and surface cross-linking can be efficiently implemented. "Drying completed" in this specification refers to a state where the solid content reaches 80% by mass. In this process, the dry polymer may sometimes be in the form of a clot, and the water content of the upper and lower parts and the center / edge of the clot may be different. In this case, the dry polymer can be appropriately obtained from different positions, crushed as needed, and then the water content is measured, and the average value is taken.

[0209] In this specification, a dried polymer that does not satisfy the above-mentioned predetermined solid content may be referred to as an “undried product.” The “dried product” in the drying step may include a particulate hydrogel.

[0210] The drying method in the drying process can include, for example, heating drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, azeotropic dehydration drying with a hydrophobic organic solvent, high humidity drying using high temperature steam, stirring drying, etc. Among them, from the viewpoint of drying efficiency, stirring drying and hot air drying are preferred. As stirring drying, stirring dryers such as paddle dryers or rotary drum dryers are preferably used. In addition, regarding hot air drying, a ventilated belt dryer for hot air drying on a ventilated belt is preferably used. Using a ventilated belt dryer can prevent the dried polymer and the granular hydrogel in the middle of the drying from being mechanically damaged and frictional to produce fine powder, etc., and dry efficiently.

[0211] From the perspective of drying efficiency, the drying temperature, i.e., the hot air temperature, in the present invention is preferably 120°C or higher, more preferably 130°C or higher, and more preferably 150°C or higher, and preferably 250°C or lower, more preferably 230°C or lower, and more preferably 200°C or lower. In addition, the drying time is selected to be 10 minutes or more, more preferably 20 minutes or more, and more preferably 30 minutes or more, and preferably 2 hours or less, more preferably 1.5 hours or less, and more preferably 1 hour or less. When the drying temperature and drying time are within this range, the physical properties of the obtained water absorbent can be within the expected range. Regarding other drying conditions, they can be appropriately set according to the moisture content, total mass and target solid content of the granular hydrogel to be dried. When belt drying is performed, the conditions described in International Publication No. 2006 / 100300, International Publication No. 2011 / 025012, International Publication No. 2011 / 025013, International Publication No. 2011 / 111657, etc. can be appropriately adopted.

[0212] (Ventilation belt dryer)

[0213] When the object to be dried is dried using a ventilated belt dryer, the object to be dried is continuously supplied to the belt of the belt dryer to form a layer (hereinafter referred to as a "gel layer"), and hot air drying is performed. The belt width of the dryer is preferably 0.5 m or more, more preferably 1 m or more, and preferably 10 m or less, more preferably 5 m or less. The belt length is selected to be 20 m or more, more preferably 40 m or more, and preferably 100 m or less, more preferably 50 m or less.

[0214] The moving speed of the object to be dried on the belt can be appropriately set according to the belt width, belt length, production volume, drying time, etc., but from the viewpoint of the load and durability of the belt driving device, the moving speed is preferably 0.3 m / minute or more, more preferably 0.5 m / minute or more, and further preferably 0.7 m / minute or more, and is preferably 5 m / minute or less, more preferably 2.5 m / minute or less, further preferably 2 m / minute or less, and particularly preferably 1.5 m / minute or less.

[0215] The average thickness of the gel layer of the dried material spread on the ventilated belt dryer is preferably 3 cm or more, more preferably 5 cm or more, and even more preferably 8 cm or more, and is preferably 30 cm or less, more preferably 20 cm or less, and even more preferably 15 cm or less. In order to effectively achieve the above solid content under the above conditions, it is preferred to control the thickness of the gel layer within the above range. On the other hand, if the gel layer is too thick, residual undried material and uneven drying are likely to occur, so that even if the above-specified drying process is performed, the proportion of dried polymer that does not meet the above preferred solid content may be high.

[0216] In the present invention, the thickness change rate obtained by the following formula in the ventilated belt dryer is preferably 1.05 or more, more preferably 1.1 or more, preferably 3 or less, more preferably 2.5 or less, and further preferably 2 or less.

[0217] Thickness change rate = (maximum thickness in the width direction of the dried material / average thickness)

[0218] Rather than making the thickness of the gel layer on the belt uniform in the width direction, it is preferred to make the thickness of the gel layer on the belt vary in the width direction. In this way, drying on the ventilation belt can achieve more uniform drying. The thickness variation rate of the gel layer refers to the cross-sectional thickness in the direction relatively perpendicular to the traveling direction of the belt, that is, the thickness of the polymerized gel in the width direction measured in a certain interval along the traveling direction of the ventilation belt. That is, the thickness of the gel layer of the present invention refers to the thickness before the drying on the ventilation belt begins, in other words, it refers to the thickness of the dried object before the solid content concentration of the dried object increases. "Before the solid content concentration increases" means: before the increase in solid content concentration relative to the solid content concentration of the dried object before drying reaches 1% by mass, more preferably before it reaches 0.5% by mass, and further preferably before it exceeds 0% by mass. In the present invention, either the gel layer thickness or the thickness variation rate may be satisfied, and preferably both are satisfied.

[0219] In the present invention, it is preferred that a thickness control operation is further performed on the dried product spread on the ventilated belt dryer. By performing the thickness control operation and preferably satisfying the aforementioned gel layer thickness, more preferably satisfying the aforementioned thickness change rate, and further preferably satisfying both the gel layer thickness and the thickness change rate, poor drying of large aggregates and the like can be further suppressed. The thickness control operation is not particularly limited as long as the thickness of the dried product on the belt can be adjusted, and examples thereof include operations performed using a rake (harrow) or a rotary leveler.

[0220] [3-5] Crushing and Classification Process

[0221] The pulverizing step is a step of pulverizing the polymer after drying, and the classification step is a step of removing fine powder from the pulverized polymer. Specifically, the dried polymer obtained by the drying step is pulverized in the pulverizing step and the particle size is adjusted to a desired range in the classification step, thereby obtaining a water-absorbing agent. By performing the pulverizing step after drying, a water-absorbing agent in a randomly crushed state (randomly crushed water-absorbing resin particles before surface cross-linking) can be obtained.

[0222] Regarding the pulverizer used in the pulverizing step, high-speed rotary pulverizers such as a roller mill, a hammer mill, a spiral mill, a pin mill, a vibration mill, an elbow-type pulverizer, a cylindrical agitator, etc. can be cited. Among them, from the viewpoint of pulverizing efficiency, a roller mill is preferably selected. In addition, a plurality of these pulverizers can also be used in combination.

[0223] As a method for adjusting the particle size in the classification process, sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)), air flow classification, etc. can be cited. Among them, sieve classification is preferably selected from the viewpoint of classification efficiency. From the viewpoint of easy pulverization, a classification process can also be additionally performed before the pulverization process.

[0224] The specific surface area of ​​the randomly fragmented water-absorbing agent (the water-absorbing agent before surface cross-linking, the randomly fragmented water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent) can be 32 m 2 / kg or more, 36m 2 / kg or more, 40m 2 / kg or more, 44m 2 / kg or more, 48m 2 / kg or more, 52m 2 / kg or more, 56m 2 / kg or more, or 60m 2 The upper limit of the specific surface area of ​​the surface-crosslinked water-absorbing agent of one embodiment of the present invention is not particularly limited, but the specific surface area may be, for example, 100 m 2 / kg or less, 80m 2 / kg or less, or 70m 2 / kg or less.

[0225] Regarding the particle size distribution of the randomly broken water-absorbing agent (the water-absorbing agent before surface crosslinking, the randomly broken water-absorbing resin particles before surface crosslinking contained in the water-absorbing agent), the mass average particle size (D50) is preferably 250 μm or more and 600 μm or less, and the proportion of particles below 150 μm is 5% by mass or less. The upper limit of the mass average particle size (D50) is preferably 550 μm, more preferably 500 μm, and further preferably 450 μm. In addition, the proportion of particles below 150 μm is preferably 4% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. In addition, the proportion of particles exceeding 710 μm is preferably 3% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less. In addition, the logarithmic standard deviation (σζ) of the particle size distribution expresses the narrowness of the particle size distribution. The logarithmic standard deviation (σζ) of the particle size distribution is preferably greater than 0.20, more preferably greater than 0.25, and further preferably greater than 0.27, and preferably less than 0.50, more preferably less than 0.45, further preferably less than 0.40, and particularly preferably less than 0.35. The smaller the value of the logarithmic standard deviation (σζ) of the particle size distribution, the more uniform the particle size, that is, the less biased the particle distribution. Preferably, the mass average particle size (D50) and the proportion of particles below 150 μm all meet the above range, more preferably the mass average particle size (D50), the proportion of particles below 150 μm, and the proportion of particles exceeding 710 μm all meet the above range, and further preferably the mass average particle size (D50), the proportion of particles below 150 μm, the proportion of particles exceeding 710 μm, and the logarithmic standard deviation all meet the above range, and appropriate combinations can be made within the above ranges.

[0226] The above-mentioned particle size requirement also applies to the water-absorbing agent after surface crosslinking (the water-absorbing resin particles in a randomly broken state after surface crosslinking contained in the water-absorbing agent). Therefore, when surface crosslinking is performed, it is preferred that the surface crosslinking treatment is performed through the surface crosslinking step in such a manner that the particle size obtained by adjusting the water-absorbing agent before surface crosslinking is maintained, and it is more preferred that a granulation step is provided after the surface crosslinking step to adjust the particle size. The water-absorbing agent that does not pass through the sieve with a mesh size of 710 μm in the classification step is preferably returned to the pulverization step and pulverized again in the pulverization step.

[0227] [3-6] Surface cross-linking process

[0228] This step is a step of further forming a portion with a high crosslinking density on the surface of the water-absorbing agent before surface crosslinking obtained through the above steps as needed, and this step includes a mixing step, a heat treatment step, a cooling step, etc. In the surface crosslinking step, free radical crosslinking, surface polymerization, and a crosslinking reaction with a surface crosslinking agent occur on the surface of the water-absorbing agent before surface crosslinking, thereby obtaining a surface crosslinked water-absorbing agent (surface crosslinked randomly broken water-absorbing resin particles contained in the water-absorbing agent).

[0229] [3-6-1] Mixing process

[0230] This step is a step of mixing a solution containing a surface crosslinking agent (hereinafter referred to as "surface crosslinking agent solution") with a water absorbing agent before surface crosslinking in a mixing device to obtain a wetted mixture.

[0231] (Surface cross-linking agent)

[0232] In the present invention, a surface crosslinking agent is used during surface crosslinking. As the surface crosslinking agent, for example, the surface crosslinking agent described in U.S. Patent No. 7183456 can be cited. Taking into account reactivity, at least one surface crosslinking agent can be selected from these surface crosslinking agents. In addition, from the viewpoints of the operability of the surface crosslinking agent and the water absorption performance of the water absorbing agent, it is preferred to select an organic compound having two or more functional groups that can react with a carboxyl group and form a covalent bond as the surface crosslinking agent.

[0233] Specific examples of the surface crosslinking agent include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,2-hex ... -hexanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,3-hexanediol, 2,4-hexanediol, glycerol, polyglycerol, diethanolamine, triethanolamine and other polyol compounds; ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine, polyethyleneimine and other polyamine compounds; halogenated epoxy compounds, condensates of polyamine compounds and halogenated epoxy compounds; oxazoline compounds such as 1,2-ethylenebisoxazoline; oxazolidine Ketone compounds; 1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2 -ketone, 4,6-dimethyl-1,3-dioxane-2-one, 1,3-dioxolane-2-one and other alkylene carbonate compounds; ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, glycidol and other polyglycidyl compounds; oxetane compounds; vinyl ether compounds; cyclic urea compounds, etc.

[0234] If multiple surface crosslinking agents are used, the total amount of the surface crosslinking agents used is preferably 0.01 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 2 parts by mass or less, relative to 100 parts by mass of the water absorbing agent before surface crosslinking. When the amount of the surface crosslinking agent used is within this range, an optimal crosslinking structure can be obtained on the surface layer of the water absorbing agent before surface crosslinking, thereby obtaining a water absorbing agent with high physical properties.

[0235] The surface crosslinking agent is preferably added to the water absorbing agent before surface crosslinking in the form of an aqueous solution. In this case, relative to 100 parts by mass of the water absorbing agent before surface crosslinking, the amount of water used is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and further preferably 0.5 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 10 parts by mass or less. When the amount of water used is within this range, the operability of the surface crosslinking agent solution can be improved, and the surface crosslinking agent is uniformly mixed into the water absorbing agent before surface crosslinking.

[0236] In addition, as needed, a hydrophilic organic solvent can be used together with the water to form the surface crosslinking agent solution. In this case, the amount of the hydrophilic organic solvent used is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and further preferably 1 part by mass or less relative to 100 parts by mass of the water absorbent before surface crosslinking. As the hydrophilic organic solvent, specifically, lower alcohols such as methanol; ketones such as acetone; ethers such as dioxane; amides such as N,N-dimethylformamide; sulfones such as dimethyl sulfoxide; polyols such as ethylene glycol, etc. However, when using these hydrophilic organic solvents, it is preferred to limit the amount used to as little as possible.

[0237] In addition, various additives described in the column "[3-7] Additives and their adding step" described later may be added to the surface crosslinking agent solution in an amount of 5 parts by mass or less, or may be added separately in a mixing step.

[0238] (Mixing method, mixing conditions)

[0239] The mixing of the water absorbing agent before surface crosslinking and the surface crosslinking agent solution may be carried out by preparing a surface crosslinking agent solution in advance and preferably spraying or dropping the solution, more preferably spraying, onto the water absorbing agent before surface crosslinking to mix.

[0240] The mixing device for carrying out the mixing preferably has a torque required for uniformly and effectively mixing the water absorbing agent before the surface crosslinking with the surface crosslinking agent. As the mixing device, a high-speed stirring type mixer is preferred, and a high-speed stirring type continuous mixer is more preferred. The number of revolutions of the high-speed stirring type mixer is preferably more than 100 rpm, more preferably more than 300 rpm, and preferably less than 10000 rpm, more preferably less than 2000 rpm.

[0241] From the viewpoint of the miscibility with the surface crosslinking agent solution and the cohesiveness of the humidified mixture, the temperature of the water absorbing agent before surface crosslinking provided to this step is preferably 35° C. or higher, and preferably 80° C. or lower, more preferably 70° C. or lower, and further preferably 60° C. or lower. In addition, the mixing time is preferably 1 second or longer, more preferably 5 seconds or longer, and preferably 1 hour or shorter, and more preferably 10 minutes or shorter.

[0242] [3-6-2] Heat treatment process

[0243] This step is a step of heating the humidified mixture obtained in the mixing step to perform a crosslinking reaction on the surface of the water absorbent before surface crosslinking. Regarding the heat treatment of the humidified mixture, the humidified mixture can be heated in a static state, or heated in a flowing state by a power such as stirring. From the point of view that the humidified mixture can be heated uniformly as a whole, it is preferably heated under stirring. From the above viewpoint, the heat treatment device for performing the heat treatment can include a paddle dryer, a multi-blade stirrer, a tower dryer, etc.

[0244] From the viewpoint of the type and amount of the surface crosslinking agent and the water absorption performance of the water absorbent, the heating temperature in this step is preferably 150°C or higher, more preferably 170°C or higher, particularly preferably 180°C or higher, and preferably 250°C or lower, more preferably 230°C or lower. In addition, the heating time is preferably at least 5 minutes, more preferably at least 7 minutes. Controlling the heating temperature and heating time within the above range can improve the water absorption performance of the obtained water absorbent, so it is preferred.

[0245] [3-6-3] Cooling process

[0246] This step is an optional step provided after the heat treatment step as needed. This step is a step of forcibly cooling the high-temperature water-absorbing agent after the heat treatment step to a predetermined temperature to rapidly stop the surface crosslinking reaction.

[0247] Regarding the cooling of the water absorbing agent, it can be cooled in a static state or in a flowing state by a power such as stirring. From the point of view that the water absorbing agent can be uniformly cooled as a whole, it is preferably cooled under stirring. From the above point of view, as a cooling device for performing the cooling, a paddle dryer, a multi-stirring blade stirrer, a tower dryer, etc. can be cited. These cooling devices can be of the same specifications as the heat treatment device used in the heat treatment process. By replacing the heat medium of the heat treatment device with a refrigerant, it can be used as a cooling device.

[0248] The cooling temperature in this step can be appropriately set depending on the heating temperature in the heat treatment step, the water absorption performance of the water absorbent, etc., and is preferably 40°C or higher, more preferably 50°C or higher, and is preferably 100°C or lower, more preferably 90°C or lower, and further preferably 70°C or lower.

[0249] [3-7] Additives and their adding process

[0250] [3-7-1] Aminocarboxylic acid chelating agent and / or phosphorus chelating agent, α-hydroxycarboxylic acid (salt)

[0251] In order to achieve the extraction amount within the range defined by formula (A) and formula (B), the method for producing the water absorbent may further include the step of adding an aminocarboxylic acid chelating agent and / or a phosphorus chelating agent and / or an α-hydroxycarboxylic acid (salt) to the surface-crosslinked water absorbent, and the embodiment including the addition step may also belong to one embodiment of the present invention. The aminocarboxylic acid chelating agent and / or a phosphorus chelating agent and the α-hydroxycarboxylic acid (salt) may be the corresponding compounds described above.

[0252] The amount of α-hydroxycarboxylic acid (salt) added is more than 0 mol% (or more than 0 mol%), preferably more than 0.04 mol%, more preferably more than 0.06 mol% (0.08 mol%), and less than 0.41 mol%, preferably less than 0.37 mol%, more preferably less than 0.33 mol%. This solution can better maintain good physical properties, especially the physical properties of AAP and SFC, and reduce the speed of discoloration over time.

[0253] In addition, relative to the amount of the unsaturated monomer containing carboxyl contained by this water absorbing agent, the addition of aminocarboxylic acid chelating agent and / or phosphorus chelating agent exceeds 0mmol% (or more than 0mmol%), is preferably more than 0.4mmol%, more preferably more than 0.8mmol%, and is preferably below 20mmol%, more preferably below 18mmol%, and then is preferably below 16mmol%, particularly preferably below 14mmol%. Through this scheme, can better both maintain good physical property, reduce the discoloration speed through with time again. On the other hand, if exceed described scope, then not only uneconomical, and the color of employed chelating agent can make the hue variation of water absorbing agent, therefore not preferred.

[0254] [3-7-2] Surface modifier

[0255] Surface modifier is an additive added to modify the particle surface of the water absorbent, specifically, liquid permeability enhancer, anti-caking agent under moisture absorption, powder flow control agent, binder of water absorbent, etc. can be cited. In particular, from the viewpoint of improving liquid permeability, at least one compound selected from polyvalent metal salts, cationic polymers, and inorganic microparticles can be used, and two or more can be used as needed. The amount of the surface modifier added can be appropriately set according to the selected compound. In order to achieve the purpose of modifying the particle surface of the water absorbent, the addition process of the surface modifier is preferably carried out after the polymerization process, more preferably after the drying process, and further preferably after the surface cross-linking process. In addition, the addition of the surface modifier can be carried out in any one or more processes.

[0256] (polyvalent metal salt)

[0257] If a polyvalent metal salt is used, the polyvalent metal cation of the polyvalent metal salt is preferably divalent or more, more preferably divalent or more, and preferably tetravalent or less, and further preferably trivalent or tetravalent. In addition, examples of polyvalent metals that can be used include aluminum, zirconium, and the like. Therefore, examples of polyvalent metal salts that can be used in this step include aluminum lactate, zirconium lactate, aluminum sulfate, zirconium sulfate, and the like. Among them, from the viewpoint of the effect of improving the flow conductivity (SFC) of the salt water, aluminum lactate or aluminum sulfate is more preferred, and aluminum sulfate is further preferred.

[0258] The amount of the polyvalent metal salt added is preferably 0 mol or more and preferably less than 3.6×10 -5 mole, more preferably less than 1.4×10 -5 mole, and preferably less than 1.0×10 -5 Moore.

[0259] In addition, the polyvalent metal-containing solution may further contain a monovalent metal compound such as sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium lactate, etc., as a regulator for regulating the permeability of the polyvalent metal into the water absorbing agent.

[0260] (Cationic polymer)

[0261] If a cationic polymer is used, the cationic polymer may be a substance described in U.S. Pat. No. 7,098,284. Among them, vinylamine polymers are more preferred from the viewpoint of improving liquid permeability. In addition, the mass average molecular weight of the cationic polymer is preferably 5,000 or more and 1,000,000 or less.

[0262] The amount of the cationic polymer added is preferably more than 0 part by mass, and is preferably less than 2.5 parts by mass, more preferably less than 2.0 parts by mass, and further preferably less than 1.0 part by mass, relative to 100 parts by mass of the water absorbing agent.

[0263] (Inorganic particles)

[0264] When inorganic fine particles are used, examples of the inorganic fine particles include those described in US Pat. No. 7,638,570. Among them, silicon dioxide is preferred from the viewpoint of improving liquid permeability.

[0265] If the primary particle size of the inorganic fine particles is less than 20 nm, the amount of the inorganic fine particles added is preferably more than 0 parts by mass, and is preferably less than 1.2 parts by mass, more preferably less than 1.0 parts by mass, and further preferably less than 0.5 parts by mass, relative to 100 parts by mass of the water absorbing agent. In addition, if the primary particle size of the inorganic fine particles is greater than 20 nm, the amount of the inorganic fine particles added is more than 0 parts by mass, and is preferably less than 2.0 parts by mass, more preferably less than 1.5 parts by mass, and further preferably less than 1.0 parts by mass, relative to 100 parts by mass of the water absorbing agent.

[0266] [3-7-3] Other additives

[0267] Other additives include reducing agents, surfactants, compounds containing phosphorus atoms, oxidizing agents, organic powders such as metal soaps, deodorants, antibacterial agents, pulp and thermoplastic fibers, terpene aromatic compounds, phenolic aromatic compounds and other aromatic substances, and one or more of these may be used.

[0268] It is preferred that other additives are added or contained in an amount within a range of 0.001 mass % or more and 1 mass % or less relative to the monomer or the water absorbing agent.

[0269] The additive may be added before or after or in the middle of at least one step selected from the aforementioned monomer aqueous solution preparation step, polymerization step, gel pulverization step, drying step, pulverization step, classification step, and surface cross-linking step. Preferably, the additive is added before or after or in the middle of any step after the polymerization step.

[0270] [3-7-4] Additive Addition Process

[0271] If the additive is added to the water absorbing agent and the additive is in the form of a liquid or a solution containing an aqueous medium such as water, it is preferred to spray the liquid or solution onto the water absorbing agent and apply sufficient torque to uniformly and reliably mix the water absorbing agent and the additive. On the other hand, if the additive is a solid such as a powder, it can be dry-mixed with the water absorbing agent, and an aqueous liquid such as water can also be used as a binder.

[0272] As for the device used for the mixing, specifically, there can be mentioned a stirring type mixer, a cylindrical mixer, a double-walled cone mixer, a V-shaped mixer, a bow tie mixer, a spiral mixer, a flow type rotating disk mixer, an air flow type mixer, a double wrist kneader, an internal mixer, a pulverizing kneader, a rotary mixer, a spiral extruder, etc. When a stirring type mixer is used, the number of revolutions is preferably 5 rpm or more, more preferably 10 rpm or more, and preferably 10000 rpm or less, more preferably 2000 rpm or less.

[0273] [3-8] Granulation process

[0274] In the present invention, in addition to the above-mentioned steps, a granulation step can also be implemented as needed. The granulation step refers to a step of adjusting the particle size of the surface cross-linked water absorbent obtained by the surface cross-linking step to the expected range, thereby obtaining a water absorbent that is in a state ready for shipment as a final product. If there is no crushing step and classification step before the surface cross-linking step, the subsequent operation after the surface cross-linking step is used as the crushing step and the classification step. The particle size adjustment method in the granulation step can adopt the same adjustment method as the classification step. In addition, if the water absorbent is agglomerated in the surface cross-linking step and the surface modifier addition step, it can be broken up, for example, after light crushing, it can be mixed, for example, using a paint shaker for mixing. Therefore, it can be classified by a sieve or the like in a manner that satisfies the expected mass average particle size (D50) and the ratio of the mass average particle size (D50).

[0275] [3-9] Other processes

[0276] In the present invention, in addition to the above steps, at least one step selected from a transportation step, a storage step, a packaging step, a custody step, etc. may be included as necessary.

[0277] The absorbent of the sanitary product of the present invention is composed of the water absorbent and the hydrophilic substrate of the present embodiment, and may further contain fiber materials such as hydrophilic fibers. The scheme of the absorbent can be: the composite containing the water absorbent and the hydrophilic fiber is further clamped by a hydrophilic substrate (hydrophilic non-woven fabric and toilet paper, etc.) to be integrated, but it is not limited to these exemplified schemes. For example, an absorbent formed by compounding the water absorbent directly on a sheet substrate such as a hydrophilic substrate (hydrophilic non-woven fabric and toilet paper, etc.) without using hydrophilic fibers can also become the absorbent of the present invention. If the absorbent contains hydrophilic fibers, from the viewpoint of giving full play to the effect of the present invention, the absorbent, for example, preferably contains a composite formed by uniformly mixing the water absorbent and the hydrophilic fibers. As such a scheme, for example, the water absorbent and the hydrophilic fiber are uniformly mixed; the water absorbent and the hydrophilic fiber are uniformly mixed and formed into a layered body, and then the hydrophilic fiber formed into a layer is further stacked on the layered body; the water absorbent and the hydrophilic fiber are uniformly mixed and formed into a layered body, and then the water absorbent is sandwiched between the layered body and the hydrophilic fiber formed into a layer. In addition, the water absorbent can also be sandwiched between the hydrophilic fibers formed into a layer, etc. In addition, a specific amount of water can be mixed with the water absorbent resin to form the water absorbent resin into a sheet, thereby forming an absorbent.

[0278] Examples of the hydrophilic substrate include sheet-like substrates such as hydrophilized polyethylene, hydrophilized polypropylene, hydrophilized polyester, and toilet paper (or a composite thereof).

[0279] Examples of the fiber material include, for example, cellulose fibers such as mechanical pulp, chemical pulp, semi-chemical pulp, and dissolving pulp obtained from wood, and hydrophilic fibers such as artificial cellulose fibers such as rayon and acetate fibers. Among these fibers, cellulose fibers are preferred. In addition, the hydrophilic fiber may contain synthetic fibers such as polyamide, polyester, and polyolefin. The fiber material is not limited to these fibers exemplified.

[0280] The mass ratio of the water absorbent in the mass of the absorbent can be 75% by mass or more, 80% by mass or more, and can be 99% by mass or less, 95% by mass or less. In addition, if the proportion of fiber materials such as hydrophilic fibers in the absorbent is small, an adhesive adhesive can be used to bond the absorbent, i.e., the hydrophilic fibers, to each other. By bonding the hydrophilic fibers to each other, the strength and shape retention of the absorbent before and during use of the absorbent can be improved. As the adhesive adhesive, hot-melt fibers such as polyolefin fibers composed of polyethylene, polypropylene, ethylene-propylene copolymers, 1-butene-ethylene copolymers, etc., and adhesive emulsions can be exemplified. These adhesive adhesives can be used alone or in combination of two or more. The weight ratio of the hydrophilic fiber to the adhesive adhesive is preferably in the range of 50 / 50 to 99 / 1, more preferably in the range of 70 / 30 to 95 / 5, and further preferably in the range of 80 / 20 to 95 / 5.

[0281] In addition, the sanitary product of the present invention may be a sanitary product in which an absorbent layer containing the above-mentioned absorbent body is sandwiched between a pad having liquid permeability and a pad having liquid non-permeability. Furthermore, since the absorbent layer of the absorbent article contains the above-mentioned absorbent body, the absorbent article has the excellent water absorption property as described above. Specifically, examples of absorbent articles include diapers, sanitary napkins, incontinence pads and other sanitary materials, but are not particularly limited. The absorbent article has excellent water absorption properties, so when the absorbent article is a diaper, for example, it can prevent urine leakage and can have a so-called dry feeling.

[0282] The gasket having liquid permeability (hereinafter referred to as liquid permeable gasket) is composed of a material having the property of being permeable to aqueous liquids. Examples of the material of the liquid permeable gasket include nonwoven fabrics; woven fabrics; porous synthetic resin films composed of polyethylene, polypropylene, polyester, polyamide, etc. The gasket having liquid impermeability (hereinafter referred to as liquid impermeable gasket) is composed of a material having the property of being impermeable to aqueous liquids. Examples of the material of the liquid impermeable gasket include: synthetic resin films composed of polyethylene, polypropylene, vinyl acetate fiber, polyvinyl chloride, etc.; films obtained from a composite material composed of a synthetic resin and a nonwoven fabric; films obtained from a composite material composed of the synthetic resin and a woven fabric, etc. The liquid impermeable gasket may also have the property of being permeable to vapor.

[0283] The embodiment of the absorbent layer is not particularly limited, and it only needs to have the absorbent body described above. In addition, the method for manufacturing the absorbent layer is not particularly limited. In addition, the method for sandwiching the absorbent layer with a liquid permeable pad and a liquid impermeable pad, that is, the method for manufacturing the absorbent article is not particularly limited. Deodorants, antibacterial agents, fragrances, various inorganic powders, foaming agents, pigments, dyes, hydrophilic short fibers, fertilizers, oxidants, reducing agents, water, salts, etc. may be added to the absorbent body to impart various functions to the absorbent body or the absorbent article.

[0284] The present invention may also be the following aspects. According to one aspect of the present invention, as an example, a water absorbing agent having a large specific surface area, good physical properties, and a reduced color change rate over time can be provided.

[0285] [1] A water-absorbing agent in a random crushed state, with a specific surface area of ​​32 m 2 / kg or more,

[0286] The plotted points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted therefrom (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent extracted therefrom (y1 mmol%) as the Y-axis are within the range defined by formula (A) and formula (B), and the water absorbent has undergone surface cross-linking.

[0287] y1≥0…Formula (A)

[0288] 0≤x1≤0.33…Formula (B)

[0289] But this does not include the following range: y1≤28.7x1 2 -11.1x1+1.07and 0≤x1<0.19.

[0290] [2] The water absorbing agent according to [1], wherein

[0291] The WI value change of the water absorbing agent before and after the following color change test is less than 40, and the WI value before the following color change test is greater than 42;

[0292] Discoloration test: The water absorbent was exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1 RH% for 7 days.

[0293] [3] The water absorbing agent according to [1] or [2], wherein the water absorbing agent satisfies the relationship between equations (3) and (4).

[0294] y2≥0.24x2+18…Formula (3)

[0295] z2≥-10x2+306…Formula (4)

[0296] (In equations (3) and (4), x2 represents CRC, y2 represents AAP, z2 represents SFC, and x2 is a value greater than or equal to 26 and less than or equal to 32).

[0297] [4] A method for producing a water absorbing agent, wherein the water absorbing agent has a specific surface area of ​​32 m 2 / kg or more of surface cross-linked random fragmented water absorbent,

[0298] The production method comprises a preparation step of preparing a monomer aqueous solution, wherein the monomer aqueous solution contains a monomer having acrylic acid (salt) as a main component and at least one polymerizable internal crosslinking agent.

[0299] In the preparation process, α-hydroxycarboxylic acid (salt) and aminocarboxylic acid chelating agent are respectively added to the monomer aqueous solution so that: the plotted points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent extracted from the water absorbing agent (y1 mmol%) as the Y-axis are within the range defined by formula (A) and formula (B).

[0300] y1≥0…Formula (A)

[0301] 0≤x1≤0.33…Formula (B)

[0302] But this does not include the following range: y1≤28.7x1 2 -11.1x1+1.07and 0≤x1<0.19.

[0303] [5] The method for producing a water absorbing agent according to [4], further comprising a surface cross-linking step and an adding step after the surface cross-linking step.

[0304] In the adding step, α-hydroxycarboxylic acid (salt) and / or aminocarboxylic acid chelating agent are added to the water absorbing agent obtained in the surface cross-linking step so that: the plotted points obtained by plotting the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the final product (x1 mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent extracted from the water absorbing agent as the final product (y1 mmol%) as the Y-axis are within the range defined by formula (A) and formula (B).

[0305] y1≥0…Formula (A)

[0306] 0≤x1≤0.33…Formula (B)

[0307] But this does not include the following range: y1≤28.7x1 2 -11.1x1+1.07 and 0≤x1<0.19.

[0308] (Example)

[0309] Hereinafter, the present invention will be described in further detail by way of Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0310] <Measurement method>

[0311] The following is an explanation of the measurement method of the water absorbent. However, if the water absorbent has been stored for a long time, or if the water absorbent is taken out from sanitary materials such as an absorbent body and a diaper, the water absorbent may contain moisture, and thus an appropriate value cannot be measured. If the moisture content of the water absorbent when it is produced is known (for example, the moisture content is recorded on the manufacturing inspection ticket), it is preferred to first dry the water absorbent under reduced pressure drying at about 80°C until the specified moisture content is reached, and then measure the water absorbent. On the other hand, if the moisture content when it is produced is unknown, it is preferred to first adjust the moisture content of the water absorbent to less than 10% by mass, and then measure the water absorbent. Regarding the method of adjusting the moisture content of the water absorbent resin (water absorbent) to less than 10% by mass, there is a method of drying the water absorbent resin (water absorbent) at 80°C and under reduced pressure (less than 10.0 kPa) for 24 hours.

[0312] (a) CRC (absorption ratio without pressure)

[0313] The CRC (absorption capacity without pressure) of the water absorbent of the present invention is measured in accordance with NWSP 241.0.R2 (15). Specifically, 0.2 g of the water absorbent is placed in a nonwoven bag, which is immersed in an excess amount of a 0.9 mass % sodium chloride aqueous solution for 30 minutes to allow the water absorbent to swell freely, and then dehydrated using a centrifugal separator (centrifugal force: 250 G), and the CRC (absorption capacity without pressure) (unit: g / g) is measured.

[0314] (b) AAP (absorption under pressure)

[0315] The AAP (absorption under pressure) of the water absorbing agent of the present invention is measured in accordance with NWSP 242.0.R2 (15). However, in the present invention, the pressure condition is changed to 4.83 kPa (49 g / cm 2 Specifically, 0.9 g of the water absorbing agent was placed at 4.83 kPa (49 g / cm 2 After swelling in an excess of 0.9 mass % sodium chloride aqueous solution under a pressure of 0.7 psi (0.7 psi) for 1 hour, the AAP (absorption capacity under pressure) (unit: g / g) was measured. That is, in this specification, AAP (absorption capacity under pressure) is the value measured under a pressure of 4.83 kPa.

[0316] (c) SFC (saline flow conductivity)

[0317] The SFC (saline flow conductivity) of the water absorbent of the present invention (unit: ×10 -7 cm 3 sec / g) was measured according to the method described in U.S. Patent No. 5,669,894. The specific procedure is as follows.

[0318] First, 1.50 g of the water absorbent was uniformly placed in a container for SFC measurement, and immersed in artificial urine for 60 minutes under a load of 2.1 kPa to obtain a swollen gel. The gel layer height (L0) of the swollen gel was measured, and then a 0.69 mass % sodium chloride aqueous solution was infiltrated through the swollen gel layer at a constant hydrostatic pressure (ΔP). During the infiltration, the swollen gel layer was kept under a load of 2.1 kPa.

[0319] During the infiltration, the amount of liquid that permeated through the gel layer was recorded for 10 minutes at 20-second intervals as a function of time using a computer and a balance.

[0320] The flow rate Fs(T) (unit: g / s) of the liquid permeating the swollen gel was obtained by dividing the increased mass (g) by the increased time. The time when the hydrostatic pressure becomes constant and the flow rate Fs becomes stable is set as Ts, and the value of Fs(T=0) (i.e., the initial flow rate Fs(T=0) permeating the swollen gel) is calculated using only Ts and the data obtained during the 10 minutes. The result of the least squares operation of Fs(T) relative to time is obtained, and the result is extrapolated with T=0 to obtain Fs(T=0).

[0321] Based on the above operation and the size of the measuring device, the SFC of the water absorbing agent was calculated by the following formula (a) (unit: ×10 -7 cm 3 ·s·g -1 ).

[0322] Formula (a): SFC = (Fs (T = 0) × L0) / (ρ × A × ΔP)

[0323] In formula (a),

[0324] Fs(T=0) is the initial flow rate through the gel layer (unit: g / s)

[0325] L0 is the height of the gel layer swollen by artificial urine (unit: cm)

[0326] ρ is the density of 0.69 mass% sodium chloride aqueous solution (unit: g / cm 3 )

[0327] A is the area of ​​the top surface of the gel layer (unit: cm 2 )

[0328] ΔP is the hydrostatic pressure (dyne / cm 2 )

[0329] In addition, if the liquid seeps through too quickly and the hydrostatic pressure cannot meet the above-mentioned constant requirement, the value of ΔP can be changed to a water pressure value calculated according to the liquid level of the sodium chloride aqueous solution to obtain SFC.

[0330] The artificial urine is obtained by dissolving 0.25 g of calcium chloride dihydrate, 2.0 g of potassium chloride, 0.50 g of magnesium chloride hexahydrate, 2.0 g of sodium sulfate, 0.85 g of diammonium hydrogen phosphate and 0.15 g of diammonium hydrogen phosphate in 994.25 g of pure water.

[0331] (d) Initial color tone and color tone after time has passed

[0332] The initial color tone and the color tone after the time of the water absorbent of the present invention are measured by Hunter Lab colorimetric system. As a measuring device, LabScan (registered trademark) XE manufactured by Hunter Lab was used, and as a measuring condition, reflection measurement was selected, and as a measuring caliber, 1 inch or 1.75 inches was selected. The size of the initial color tone measurement container is changed according to the measuring caliber (if the measuring caliber is 1 inch, the container size is 5.5 cm inner diameter and 1 cm height, and if the measuring caliber is 1.75 inches, the container size is 9.5 cm inner diameter and 0.6 cm height), and the material of the initial color tone measurement container is aluminum or stainless steel.

[0333] Next, the water absorbing agent was placed in the initial color tone measurement container and filled until the water absorbing agent overflowed the container. The water absorbing agent that protruded beyond the top surface of the container was smoothed with a ruler or the like. The L value, a value, b value, WI value, and YI value of the surface of the water absorbing agent were measured at room temperature (20 to 25°C) and a relative humidity of 50% RH.

[0334] If the water absorbing agent is a water absorbing agent just produced or before shipment (usually), or a water absorbing agent stored at an atmosphere of 30°C or less and 50% RH for no more than 1 year after production, its color tone is regarded as the "initial color tone".

[0335] In addition, if the water absorbing agent is a water absorbing agent that has been subjected to the following color change acceleration test, the color tone is referred to as the "color tone after the passage of time".

[0336] In the discoloration promotion test, 12 - 14 g of the water absorbent uniformly filled in a Petri dish was exposed for 7 days in a thermo-hygrostat (small environmental tester; model SH-641 / Espec Corporation) adjusted to a temperature of 70 ± 1°C and a relative humidity of 75 ± 1% RH. The Petri dish used can achieve a tight connection between the upper dish and the lower dish by its own weight when static, thereby achieving moderate sealing. Its size is an inner diameter of 90 mm and a height of 15 mm, and its material is plastic. As a specific example of the Petri dish used, the model manufactured by BIO-BIK Company: I-90 can be cited.

[0337] (e) Initial hue of the simulated absorber and hue after the passage of time

[0338] A method for evaluating the hue when imagining the actual use of sanitary products such as diapers will be described. Basically, it is carried out according to the method shown in the column of "(d) Initial hue and hue after the passage of time", but when measuring the initial discoloration and the discoloration after the passage of time using the Hunter Lab colorimetric system, the measurement was carried out in such a way that filter paper was overlapped and covered on the absorber in each container. The filter paper used is qualitative filter paper (specification: No.2·Φ110mm) manufactured by ADVANTEC Company. The filter paper was pre-cut so that it could be accommodated in the measurement container for the initial hue and the measurement container for the discoloration after the passage of time. The change amount between the initial hue and the hue after the passage of time is shown by the following formula.

[0339] ΔWI (change amount) = |WI (hue after the passage of time; after the discoloration test) - WI (initial hue; before the discoloration test)|

[0340] (f) FSR (water absorption rate)

[0341] Regarding the surface-crosslinked water absorbent of an embodiment of the present invention, the water absorption rate (FSR) of 1 g of the water absorbent with respect to 20 g of physiological saline is 0.31 g / g / s or more, more preferably 0.34 g / g / s or more, and still more preferably 0.37 g / g / s or more. There is no particular limitation on the upper limit of the water absorption rate (FSR), but generally it is 1.0 g / g / s. The measurement method of FSR is specified in Pamphlet No. WO2009 / 016055.

[0342] (g) Specific surface area

[0343] By the following method, the specific surface area of the water absorbent was obtained by analyzing the images taken by X-ray CT using analysis software.

[0344] <X-ray CT imaging>

[0345] 1.0 g of the water absorbing agent of the present invention was placed in a resin container (container No. 1, 2.5 mL; manufactured by Maruemu Corporation), and was shaken thoroughly to prevent uneven distribution, and then measured using a microfocus X-ray CT system inspeXio SMX-100CT manufactured by Shimadzu Corporation. The measurement conditions are as follows.

[0346] · Horizontal image size (pixel): 512

[0347] Image vertical size (pixel): 512

[0348] X-ray tube voltage (kV): 50

[0349] X-ray tube current (μA): 40

[0350] Inch size: 4.0

[0351] X-ray filter: None

[0352] SDD (distance between the focus of the X-ray source and the X-ray detector) (mm): 500

[0353] SRD (distance between the focus of the X-ray source and the rotation center of the measurement sample) (mm): 40

[0354] Scanning mode 1: CBCT

[0355] Scan mode 2: Regular scan

[0356] Scanning angle: full scan

[0357] Number of observations: 1200

[0358] Average: 5

[0359] Leveling: YZ

[0360] Layer thickness (mm): 0.008

[0361] Layer spacing (mm): 0.010

[0362] Zoom rate: 50

[0363] BHC data: None

[0364] High-precision mode: Yes

[0365] FOV XY (maximum imaging area XY) (mm): 5

[0366] FOV Z (maximum imaging area Z) (mm): 4

[0367] · 3D pixel size (mm / voxel): 0.010

[0368] <Calculation of specific surface area>

[0369] The X-ray CT imaging data were analyzed in the following procedure using analysis software TRI / 3D-PRT-LRG manufactured by Ratoc System Engineering Co., Ltd.

[0370] 1. Select Particle Measurement, 3D Particles, Particle Separation, and Giant Particle Separation from the menu. This operation displays the EV screen, BC screen, EVC screen, and giant particle separation screen.

[0371] 2. Select LW in the "Binarize" tab on the EVC screen, and change the L value to select a circular measurement target area. After selecting the measurement target area, press "Execute" to perform the process on all layered images (the result is that a cylindrical measurement area is selected as a whole). After this operation, press "ROI OK" on the giant particle separation screen.

[0372] 3. Select LW in the "Binarize" tab on the EVC screen and set the L value to 37580. This operation selects only the water absorbent particles. Next, press "Execute". Then, select "bD" on the BC screen and press "Store".

[0373] 4. Select the "ErsSml" tab in the "Binary" tab of the EVC screen. Set the grain size to 10 and press "Execute". This operation removes the minor noise.

[0374] 5. Select the "Invert" tab in the "Binary" tab of the EVC screen, and press "Execute". Then select the "ErsSml" tab of the EVC screen, set the particle size to 10, and press "Execute". Then select the "Labeling" tab of the EVC screen, select "Volume, Max", set the tiny particle size to 100, and press "Execute". Select the "Invert" tab again, and press "Execute". This operation removes the smaller noise within the particles, so that the independent cavities (voids) are filled. Next, press "Particle Separation Object OK" on the giant particle separation screen. Through this operation, the object area is saved in "b1" of the BC screen.

[0375] 6. Using the "L Op" tab (inter-channel logical operation processing) on ​​the EVC screen, "bD" was subtracted from "b1". Next, the "ErsSml" tab was selected on the "Binary" tab on the EVC screen, the particle size was set to 10, and "Execute" was pressed. This operation extracted the independent cavity. Next, "b6" on the BC screen was selected, and "Save" was pressed.

[0376] 7. Select "b1" on the BC screen and press "Display". Next, select "Small Particle Extraction" on the giant particle separation screen (do not select large particle extraction), set "Waist Ratio", "Repair Filter Size", and "Repair Mrg Sml Diameter" to 0, and press "Exec". Through this operation, the particles are separated and color-coded.

[0377] 8. Select the "Labeling" tab in the "3D" tab of the EVC screen, select the coordinate value (loop), set the microparticle size to 10, and press "Execute". Through this operation, the particles are color-coded and classified again in the order of coordinate values.

[0378] 9. From the menu, select Particle Measurement, Void in 3D Particles, and Measure after Separation. After separation, the measurement screen is displayed. Select "Edge Particle Removal", "Surface Area Calculation", "Void Calculation", select "Binary 5ch" in "Specify ROI to Calculate", press "Register OK", and select the folder to save the data. Next, press "Latest Registered Data Execution" to perform the calculation process.

[0379] 10. Based on the calculation results obtained, the specific surface area was calculated by the following formula.

[0380] Specific surface area (m 2 / kg) = total surface area of ​​particles (mm 2 ) / 〔{total volume of particles (mm 3 )-Total cavity volume (mm 3 )}×True density (g / cm 3 )〕

[0381] (h) True density

[0382] The diameter of the closed bubbles inside the water-absorbent resin is usually 1 to 300 μm. When pulverizing, the area near the closed bubbles is pulverized first. Therefore, if the water-absorbent resin is pulverized to a particle size of less than 45 μm, the obtained water-absorbent resin powder contains almost no closed bubbles. Therefore, the dry density of the water-absorbent resin powder pulverized to less than 45 μm is evaluated as the true density. That is, 10.0 g of the water-absorbent resin powder and 500 g of a cylindrical magnetic grinding column (diameter 13 mm, length 13 mm) were placed in a ball mill (manufactured by TERAOKA Co., Ltd.; model No. 90; inner diameter 80 mm, inner height 75 mm, outer diameter 90 mm, outer height 110 mm) and then ground at 60 Hz for 7 hours to obtain a water-absorbent resin that can pass through a JIS standard sieve with a mesh size of 45 μm (particle size less than 45 μm). 3.5 g of the water-absorbent resin powder having a particle size of less than 45 μm was allowed to stand in a windless dryer at 180° C. for more than 3 hours until the water content of the water-absorbent resin powder became 1% by weight or less and the powder was sufficiently dried. The dry density was then measured using a dry automatic density meter (AccuPycII 1340TC-10CC; manufactured by Shimadzu Corporation; helium as carrier gas). The measured value was used as the “true density” in the present invention.

[0383] (i) Moisture absorption rate

[0384] The empty weight (g1) of the petri dish to be used is measured, and then 3±0.01 g (g2) of the water absorbent is put in. The protruding water absorbent inside the container is scraped flat with a ruler or the like. The size of the petri dish used is 90 mm in inner diameter and 15 mm in height, and the material is plastic. As a specific example of the petri dish used, the model number: I-90 manufactured by BIO-BIK can be cited.

[0385] The metal mesh attached to the constant temperature and humidity machine (manufactured by ESPEC Co., Ltd.; Model SH-641) was placed on the protrusion located 18.5 cm above the bottom of the chamber, and the constant temperature and humidity machine was adjusted to a temperature of 40±1°C and a relative humidity of 75% RH. After the constant temperature and humidity machine was set, a petri dish containing a water-absorbing material was placed on the Figure 3 The two places indicated by the circles. Specifically, two petri dishes were arranged horizontally so that they faced each other at the center of the metal mesh, and then left to stand for 1 hour. The average value of the measured values ​​at the two places for the same sample was used as the moisture absorption rate. Here, during the measurement, the lid attached to the petri dish was not covered, and moisture absorption was performed in an open system.

[0386] After 1 hour, the Petri dishes containing the water absorbent placed at two locations were taken out and left to stand for 30 minutes at room temperature (20-25°C) and a relative humidity of 15±5%RH. The weight (g3) of the Petri dishes containing the water absorbent after moisture absorption was measured, and the moisture absorption rates were derived according to the following formula.

[0387] (moisture absorption rate) = {(g3)-(g 2) -(g1)}×1000 / (g2)

[0388] Unit: mg / g / h

[0389] The values ​​of g1, g2, and g3 are accurate to the fourth decimal place. The average value of each moisture absorption rate is used as data.

[0390] (j) Determination method of α-hydroxycarboxylic acid (salt) content of water-absorbing agent

[0391] The quantitative method of α-hydroxycarboxylic acid (salt) in the water absorbing agent of the present invention is not particularly limited, and for example, the soluble component can be extracted from the water absorbing agent and the soluble component can be analyzed by high performance liquid chromatography for quantitative determination. Specifically, the quantitative determination can be performed by the following method.

[0392] (Extraction of soluble components)

[0393] 1.0 g of the water absorbing agent of the present invention was added to 100 mL of a 0.9 mass % sodium chloride aqueous solution and stirred at 500 rpm for 1 hour. The supernatant of the obtained solution was filtered using a syringe filter (manufactured by GL SCIENCES Co., Ltd., water system <Type A>, model 25A, pore size 0.45 μm) to obtain an extraction solution.

[0394] (Quantitative analysis based on HPLC)

[0395] The high performance liquid chromatography method for quantitatively determining α-hydroxycarboxylic acid (salt) can be, for example, the following scheme.

[0396] Pump: L-7110 (manufactured by Hitachi High Technologies Co., Ltd.), flow rate 1.0 mL / min

[0397] Automatic sampler: L-7200 (manufactured by Hitachi High Technologies Co., Ltd.), injection volume 50 μL

[0398] Column heater: L-7300 (manufactured by Hitachi High Technologies Co., Ltd.), temperature setting 30°C

[0399] Differential refractometer: L-7490 (manufactured by Hitachi High Technologies, Ltd.) Column: Shim-pack SCR-101H (manufactured by Shimadzu GLC, Ltd.)

[0400] Guard column: Shim-pack SCR (H) (manufactured by Shimadzu GLC Corporation)

[0401] Mobile phase: 0.36wt% phosphoric acid aqueous solution

[0402] First, the α-hydroxycarboxylic acid (salt) to be determined is dissolved in a 0.9 mass % sodium chloride aqueous solution to prepare an α-hydroxycarboxylic acid (salt) solution of any concentration. The solution is analyzed by the high performance liquid chromatography method of the above scheme, and a scalar line is prepared based on the relationship between the α-hydroxycarboxylic acid (salt) concentration and the peak area of ​​the obtained chromatogram.

[0403] Next, the extract solution was analyzed by high performance liquid chromatography, and the amount of α-hydroxycarboxylic acid (salt) was calculated based on the relationship between the peak area and the scalar line in the obtained chromatogram.

[0404] The quantitative results are reported in the following examples.

[0405] (k) Determination of the content of diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na) in water absorbent

[0406] The chelating agent in the water absorbing agent is extracted and analyzed by the method described in the patent document (International Publication No. 2015 / 053372 Pamphlet), thereby obtaining the diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) content of the water absorbing agent of the present invention.

[0407] Specifically, 1 g of the particulate water absorbing agent was added to 100 g of physiological saline (0.9 mass % sodium chloride aqueous solution), and stirred at room temperature for 1 hour (stirring speed: 500±50 rpm) to extract the chelating agent into the physiological saline to obtain an extraction solution.

[0408] The supernatant of the obtained extraction solution was then passed through a HPLC sample pretreatment filter (chromatographic disk 25A, water-based type, filter diameter 0.45 μm; manufactured by Kurabo Co., Ltd.), and the chelating agent content in the filtrate was measured using high performance liquid chromatography (HPLC).

[0409] The chelating agent content in the particulate water absorbing agent was determined by using the scalar line measured for a monomer standard solution with a known concentration as an external reference and taking into account the dilution ratio of the particulate water absorbing agent to the physiological saline. Quantification was performed under the HPLC measurement conditions shown below.

[0410] Determination conditions:

[0411] <Eluent> A mixed solution consisting of 0.3 ml of 0.4 mol / L alum aqueous solution, 450 ml of 0.1 N potassium hydroxide aqueous solution, 3 ml of 0.4 mol / L tetra-n-butylammonium hydroxide aqueous solution, 3 ml of sulfuric acid, 1.5 ml of ethylene glycol, and 2550 ml of ion exchange water

[0412] <Column> LichroCART 250-4Superspher 100RP-18e (4μm) (manufactured by Merck Corporation)

[0413] <Column temperature>23±2℃

[0414] <Flow rate>1ml / min

[0415] <Detector>UV, wavelength 258nm

[0416] Since the chelating agent content is affected by the water content, in the present invention, the chelating agent content is a converted value per 100 parts by mass of the solid content of the water absorbing agent after correction based on the water content.

[0417] If the chelating agent added to the water absorbing agent is anionic, for ease of understanding, the salt compound of the added chelating agent is considered to remain in the water absorbing agent without undergoing salt exchange.

[0418] <Manufacturing example>

[0419] [Production Example 1]

[0420] As a production apparatus of a water-absorbing agent according to one embodiment of the present invention, a continuous production apparatus is prepared, which includes an apparatus for performing polymerization, gel grinding, drying, grinding, classification, surface cross-linking (mixing, heating treatment, cooling) and granulation, a conveying apparatus for connecting these treatments, and other auxiliary equipment. In the raw material acrylic acid, the content of methoxyphenols is 10 to 70 ppm, the content of Fe is 0.3 ppm or less, and the total content of protoanemonin, allyl acrylate, allyl alcohol, aldehyde components, maleic acid, and benzoic acid is 10 ppm or less.

[0421] First, a monomer aqueous solution (a) containing 300 parts by mass of acrylic acid, 125.2 parts by mass of a 48% sodium hydroxide aqueous solution (Fe content: 1 ppm), 0.76 parts by mass of polyethylene glycol diacrylate (average n number: 9), 18.4 parts by mass of a 0.1% diethylenetriamine pentacetic acid·trisodium (DTPA·3Na) aqueous solution (0.96 mmol% relative to the unsaturated monomer containing a carboxyl group), 1.1 parts by mass of a 50% D,L-malic acid aqueous solution (0.10 mol% relative to the unsaturated monomer containing a carboxyl group), and 226.8 parts by mass of deionized water was prepared. Here, the monomer aqueous solution (a) was temperature-controlled to about 40°C.

[0422] Next, the monomer aqueous solution (a) was continuously supplied to the polymerization device using a liquid feeding pump. Here, during the supply, 130.8 parts by mass of a 48% by mass sodium hydroxide aqueous solution was additionally supplied to the monomer aqueous solution (a), and the mixture was mixed by a static mixer provided in the pipeline, and then 14.6 parts by mass of a 4% by mass sodium persulfate aqueous solution as a polymerization initiator was further added, and the mixture was mixed by a static mixer provided in the pipeline. As the polymerization device, a flat circulating belt polymerization device with weirs at both ends was used.

[0423] After the monomer aqueous solution (a) to which the polymerization initiator was added was supplied to the polymerization device, polymerization was started. The polymerization was continued to obtain a ribbon-shaped hydrogel crosslinked polymer (hereinafter referred to as "hydrogel") (a). The polymerization time was 3 minutes.

[0424] The hydrogel (a) obtained by the polymerization step is cut into an appropriate size. Then, a constant amount of the hydrogel (a) per unit time is supplied to a screw extruder having a porous plate at the extrusion port to pulverize the hydrogel (a) to obtain a granular hydrogel (a) (screw rotation speed: 110 rpm).

[0425] Next, the granular water-containing gel (a) obtained by the gel crushing step is dried in a continuous air-belt dryer (185° C., 29 minutes). Thus, a dry polymer (a) is obtained. Next. The dry polymer (a) is continuously supplied to a roll mill for crushing, and is classified using JIS standard sieves with mesh sizes of 850 μm and 180 μm, respectively. Thus, a randomly crushed water-absorbing agent (water-absorbing agent before surface cross-linking) (a) is obtained.

[0426] Next, a surface crosslinking agent solution containing 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, 0.02 parts by mass of DENACOL (trade name) and 2.1 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the water absorbing agent (a) before surface crosslinking, and the obtained mixture was heat-treated at 185° C. for 35 minutes to obtain a surface crosslinked water absorbing agent (a).

[0427] [Production Example 2]

[0428] Into a 2-liter polypropylene container, 398.6 g of acrylic acid, 26.03 g of a 10% by mass polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) as an internal crosslinking agent (0.085 mol %), 1.29 g of a 2.0% by mass diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution (0.96 mmol %) relative to the carboxyl group-containing unsaturated monomer), 1.55 g of a 50% by mass D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industries, Ltd., food additive grade) (0.10 mol %) relative to the carboxyl group-containing unsaturated monomer), 173.9 g of a 48.5% by mass sodium hydroxide aqueous solution, and 401.6 g of deionized water (ion exchange water) were charged and mixed to prepare a monomer aqueous solution (b').

[0429] Next, the monomer aqueous solution (b') was cooled while stirring. When the liquid temperature reached 39°C, 178.7 g of a 48.5 mass % sodium hydroxide aqueous solution adjusted to 40°C was added and mixed, thereby preparing a monomer aqueous solution (b). Among them, due to the second stage neutralization heat just after the preparation was completed, the temperature of the monomer aqueous solution (b) rose to 76.5°C. In addition, immediately after the mixing of the 48.5 mass % sodium hydroxide aqueous solution was started, a precipitate was initially observed, but then the precipitate gradually dissolved, and finally a transparent uniform solution was obtained.

[0430] Next, 18.4 g of a 4.5% by mass sodium persulfate aqueous solution was added to the stirred monomer aqueous solution (b), and the mixture was immediately poured into a stainless steel cylinder-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open system. Here, the time from the start of the second stage neutralization to the pouring of the monomer aqueous solution (b) into the cylinder-shaped container was set to 1 minute, and the cylinder-shaped container was heated with a hot plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0431] After the monomer aqueous solution (b) is poured into the cylinder-shaped container, the polymerization reaction starts within 60 seconds. During the polymerization reaction, water vapor is generated while expanding and bubbling in all directions, thereby continuously polymerizing, and then the reaction product (water-containing gel (b)) shrinks to a size slightly larger than the bottom surface of the cylinder-shaped container. After 2 minutes have passed since the start of the polymerization reaction, the water-containing gel (b) is taken out. Among them, this series of operations are carried out in an open atmosphere system.

[0432] The hydrogel (b) obtained in the polymerization reaction was pulverized with a meat grinder (32 type, die diameter 6.4 mm, manufactured by Hiraga Manufacturing Co., Ltd.) to obtain a granular hydrogel (b).

[0433] Among them, the amount of the aqueous gel (b) added to the meat grinder is 4640 g / min. While adding the aqueous gel (b), deionized water adjusted to 90°C is added to the meat grinder at an amount of 60 g / min and steam is added to the meat grinder at an amount of 106 g / min, and the gel is crushed.

[0434] The refined water-containing gel (b) was spread on a 50-mesh metal net and hot-air dried at 190°C for 30 minutes. The dried product was crushed with a roll mill (WML type roll mill, Inoguchi Giken Co., Ltd.), and then sieved with JIS sieves with mesh sizes of 710 μm, 600 μm, 500 μm, 425 μm, 300 μm, 150 μm, and 45 μm, respectively, to obtain a randomly crushed water-absorbing agent (water-absorbing agent before surface cross-linking) (b) with a mass average particle size (D50) of 370 μm.

[0435] A surface crosslinking agent solution containing 0.65 parts by mass of triethylene glycol, 0.23 parts by mass of 1,6-hexanediol (manufactured by Ube Industries, Ltd.), 2.63 parts by mass of deionized water (ion exchange water), and 0.01 parts by mass of 10% polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) was added to 100 parts by mass of the water absorbing agent (b) before surface crosslinking, and the mixture was uniformly mixed. Then, the mixture was heated at 200° C. for 35 to 55 minutes to perform surface crosslinking.

[0436] After the heat treatment, the surface cross-linked water absorbent (b") was pulverized to a size that could pass through a JIS standard sieve with a mesh size of 850 μm, thereby obtaining a surface cross-linked water absorbent (b'). 35 g of the surface cross-linked water absorbent (b') and 10 g of the beads were placed in a 225 mL bottle, and the mixture was mixed for 20 minutes by vibration of a paint shaker (manufactured by Toyo Seiki Co., Ltd.), thereby obtaining a surface cross-linked water absorbent (b).

[0437] Unless otherwise noted, the raw material compounds, reaction reagents and solvents used in the Examples and Comparative Examples were all commercially available products (for example, products sold by Nippon Shokubai Co., Ltd.).

[0438] <Comparative Example>

[0439] [Comparative Example 1]

[0440] The surface-crosslinked water absorbing agent (a) obtained by the method of Production Example 1 was used as a comparative water absorbing agent (1). Tables 3 and 4 show the performance of the comparative water absorbing agent (1).

[0441] [Comparative Example 2]

[0442] The surface-crosslinked water absorbing agent (b) obtained by the method of Production Example 2 was used as a comparative water absorbing agent (2). Tables 3 and 4 show the performance of the comparative water absorbing agent (2).

[0443] [Comparative Example 3]

[0444] In the same manner as in Preparation Example 2, except that the amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) added was changed to 30.63 g (0.1 mol % relative to the unsaturated monomer containing a carboxyl group), and the amount of 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) added was changed from 1.55 g to 10.32 g (0.10 mol % relative to the unsaturated monomer containing a carboxyl group) was changed to 0.66 mol %. The obtained surface cross-linked water absorbent was used as a comparative water absorbent (3). The performance of the comparative water absorbent (3) is shown in Tables 3 and 4.

[0445] [Comparative Example 4]

[0446] In the same manner as in Preparation Example 2, except that the amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) added was changed to 28.79 g (0.094 mol % relative to the unsaturated monomer containing a carboxyl group), and the amount of 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) added was changed from 1.55 g to 7.22 g (0.10 mol % to 0.46 mol % relative to the unsaturated monomer containing a carboxyl group), the operation was carried out. The surface cross-linked water absorbent obtained was used as comparative water absorbent (4). The properties of the comparative water absorbent (4) are shown in Tables 3 and 4.

[0447] [Comparative Example 5]

[0448] In the same manner as in the preparation example 2, the addition amount of the 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 24.50 g (0.08 mol % relative to the unsaturated monomer containing a carboxyl group), the addition amount of the diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na) aqueous solution was changed from 1.29 g to 5.16 g (from 0.96 mmol % to 3.84 mmol % relative to the unsaturated monomer containing a carboxyl group), and the 50 mass % D, L-malic acid aqueous solution (manufactured by Fuso Chemical Industries, Ltd., food additive grade) was not added. The obtained surface cross-linked water absorbent was used as a comparative water absorbent (5). The performance of the comparative water absorbent (5) is shown in Tables 3 and 4.

[0449] [Comparative Example 6]

[0450] In the same manner as in Preparation Example 2, the addition amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 27.56 g (0.09 mol % relative to the unsaturated monomer containing a carboxyl group), the addition amount of 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) was changed from 1.55 g to 3.10 g (0.10 mol % relative to the unsaturated monomer containing a carboxyl group was changed to 0.20 mol %), and the diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution was not added. The obtained surface cross-linked water absorbent was used as comparative water absorbent (6). The performance of the comparative water absorbent (6) is shown in Tables 3 and 4.

[0451] <Example>

[0452] [Example 1]

[0453] In the same manner as in Preparation Example 2, except that the amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) added was changed to 24.50 g (0.08 mol % relative to the unsaturated monomer containing a carboxyl group), 50 mass % D, L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) was not added, and the amount of diethylenetriamine pentacetic acid·trisodium (DTPA·3Na) aqueous solution added was changed from 1.29 g to 10.32 g (from 0.96 mmol % to 7.68 mmol % relative to the unsaturated monomer containing a carboxyl group), the operation was carried out in the same manner as in Preparation Example 2. The surface cross-linked water absorbing agent obtained was used as water absorbing agent (1). The properties of the water absorbing agent (1) are shown in Tables 1 and 2.

[0454] [Example 2]

[0455] Based on Production Example 2, the same operation as in Production Example 2 was performed except that the amount of diethylenetriamine pentacetic acid 3 sodium (DTPA 3Na) aqueous solution added was changed from 1.29 g to 5.16 g (from 0.96 mmol% to 3.84 mmol% relative to the unsaturated monomer containing a carboxyl group).

[0456] The obtained surface-crosslinked water absorbing agent was designated as water absorbing agent (2). The properties of the water absorbing agent (2) are shown in Tables 1 and 2.

[0457] [Example 3]

[0458] The same operation as in Preparation Example 2 was performed except that the amount of diethylenetriamine pentacetic acid 3 sodium (DTPA 3Na) aqueous solution added was changed from 1.29 g to 2.58 g (from 0.96 mmol% to 1.92 mmol% relative to the unsaturated monomer containing a carboxyl group). The surface-crosslinked water-absorbing agent obtained was used as water-absorbing agent (3). The properties of the water-absorbing agent (3) are shown in Tables 1 and 2.

[0459] [Example 4]

[0460] In the same manner as in Preparation Example 2, except that the amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) added was changed to 28.79 g (0.090 mol % relative to the unsaturated monomer containing a carboxyl group), and the amount of 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) added was changed from 1.55 g to 3.10 g (0.10 mol % relative to the unsaturated monomer containing a carboxyl group was changed to 0.20 mol %), the operation was carried out. The surface cross-linked water absorbing agent obtained was used as water absorbing agent (4). The properties of the water absorbing agent (4) are shown in Tables 1 and 2.

[0461] [Example 5]

[0462] In the same manner as in the preparation example 2, the addition amount of the 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 30.63 g (0.10 mol % relative to the unsaturated monomer containing a carboxyl group), the addition amount of the 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) was changed from 1.55 g to 4.13 g (0.26 mol % relative to the unsaturated monomer containing a carboxyl group), and the diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution was not added. The obtained surface cross-linked water absorbing agent was used as the water absorbing agent (5). The properties of the water absorbing agent (5) are shown in Tables 1 and 2.

[0463] [Example 6]

[0464] In the same manner as in Preparation Example 2, except that the amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) added was changed to 32.16 g (0.105 mol % relative to the unsaturated monomer containing a carboxyl group), the amount of 50 mass % D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade) added was changed from 1.55 g to 6.19 g (0.10 mol % relative to the unsaturated monomer containing a carboxyl group was changed to 0.40 mol %), and the amount of diethylenetriamine pentacetic acid·trisodium (DTPA·3Na) aqueous solution added was changed from 1.29 g to 2.58 g (0.96 mmol % relative to the unsaturated monomer containing a carboxyl group was changed to 1.92 mmol %), the operation was carried out. The surface cross-linked water absorbing agent obtained was used as water absorbing agent (6). The properties of the water absorbing agent (6) are shown in Tables 1 and 2.

[0465] [Example 7]

[0466] In the same manner as in Preparation Example 2, the addition amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 30.63 g (0.1 mol % relative to the unsaturated monomer containing a carboxyl group), 5.78 g (0.33 mol % relative to the unsaturated monomer containing a carboxyl group) of 30 mass % lactic acid aqueous solution (adjusted with ion exchange water for use) was added instead of 50 mass % D,L-malic acid aqueous solution, and the addition amount of diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution was changed from 1.29 g to 3.87 g (changed from 0.96 mmol % to 2.88 mmol % relative to the unsaturated monomer containing a carboxyl group). The obtained surface cross-linked water absorbing agent was used as water absorbing agent (7). The properties of the water absorbing agent (7) are shown in Tables 1 and 2.

[0467] [Example 8]

[0468] In the same manner as in Preparation Example 2, the addition amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 30.63 g (0.1 mol % relative to the unsaturated monomer containing a carboxyl group), 3.59 g of 60 mass % sodium lactate aqueous solution (manufactured by Puracal) was added instead of 50 mass % D,L-malic acid aqueous solution (0.33 mol % relative to the unsaturated monomer containing a carboxyl group), and the addition amount of diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution was changed from 1.29 g to 3.87 g (from 0.96 mmol % to 2.88 mmol % relative to the unsaturated monomer containing a carboxyl group). The obtained surface cross-linked water absorbing agent was used as water absorbing agent (8). The properties of the water absorbing agent (8) are shown in Tables 1 and 2.

[0469] [Example 9]

[0470] In the same manner as in Preparation Example 2, the addition amount of 10 mass % polyethylene glycol diacrylate acrylic acid solution (molecular weight 523) was changed to 30.63 g (0.1 mol % relative to the unsaturated monomer containing a carboxyl group), 4.88 g (0.33 mol % relative to the unsaturated monomer containing a carboxyl group) of 30 mass % glycolic acid aqueous solution (manufactured by Kanto Chemical Co., Ltd., used after adjusting the concentration with ion exchange water) was added instead of 50 mass % D,L-malic acid aqueous solution, and the addition amount of diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution was changed from 1.29 g to 3.87 g (changed from 0.96 mmol % to 2.88 mmol % relative to the unsaturated monomer containing a carboxyl group). The obtained surface cross-linked water absorbing agent was used as water absorbing agent (9). The properties of the water absorbing agent (9) are shown in Tables 1 and 2.

[0471] [Example 10]

[0472] On the basis of Production Example 2, after surface cross-linking, the surface cross-linked water absorbent was crushed to a size that could pass through a JIS standard sieve with a mesh size of 850 μm, thereby obtaining a surface cross-linked water absorbent (10″′). 30 g of the surface cross-linked water absorbent (10″′) and 10 g of beads were placed in a bottle with a capacity of 225 mL, and mixed for 10 minutes by vibration of a paint stirrer (manufactured by Toyo Seiki Co., Ltd.), thereby obtaining a surface cross-linked water absorbent (10″). Then, an aqueous solution containing 1 part by mass of water and 0.01 part by mass of diethylenetriamine, 5-acetic acid, and 3-sodium was uniformly mixed with 100 parts by mass of the surface cross-linked water absorbent (10″), and then dried at 60° C. for 30 minutes. After the drying treatment, the dried product was crushed to a size that could pass through a JIS standard sieve with a mesh size of 850 μm, thereby obtaining a surface cross-linked water absorbent (10′). 30 g of the surface cross-linked water absorbent (10') and 10 g of the beads were placed in a 225 mL bottle and mixed for 10 minutes by shaking a paint shaker (manufactured by Toyo Seiki Co., Ltd.). The obtained surface cross-linked water absorbent was referred to as water absorbent (10). The properties of the water absorbent (10) are shown in Tables 1 and 2.

[0473] [Example 11]

[0474] On the basis of Example 8, (1) the amount of a 60 mass % sodium lactate aqueous solution (manufactured by Puracal) added was changed from 3.59 g (0.33 mol % relative to the unsaturated monomer containing a carboxyl group) to 0.69 g (0.063 mol % relative to the unsaturated monomer containing a carboxyl group); (2) instead of adding a diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na) aqueous solution, 5.16 g (4.04 mmol % relative to the unsaturated monomer containing a carboxyl group) of a 2.0 mass % ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP) aqueous solution was added. ; (3) Nitrogen was introduced into the monomer aqueous solution (b') at 39°C using a Kinoshita glass ball filter (filter particle No. 4; manufactured by Kinoshita Rika Kogyo Co., Ltd.) at a pressure of 0.1 MPa and a flow rate of 0.1 L / min for 5 seconds; (4) A surface crosslinking agent solution containing 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, 2.7 parts by mass of deionized water (ion exchange water), and 0.01 parts by mass of 10% polyoxyethylene (20) sorbitan monostearate was added to 100 parts by mass of the water absorbent (b) before surface crosslinking, and the mixture was uniformly mixed. Except for this, the same operation as in Example 8 was performed. The surface crosslinked water absorbent obtained was used as the water absorbent (11). The properties of the water absorbent (11) are shown in Tables 1 and 2.

[0475] [Example 12]

[0476] On the basis of Example 8, (1) the amount of 60 mass % sodium lactate aqueous solution (manufactured by Puracal) added was changed from 3.59 g (0.33 mol % relative to the unsaturated monomer containing a carboxyl group) to 1.29 g (0.12 mol % relative to the unsaturated monomer containing a carboxyl group); (2) instead of adding diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na) aqueous solution, 2.0 mass % ethylenediaminetetraacetic acid (EDTA) (manufactured by Chelest Co., Ltd., trade name: Chelest 3B) 5.16g of aqueous solution (4.74mmol% relative to the unsaturated monomer containing a carboxyl group); (3) With respect to 100 parts by mass of the water absorbent (b) before surface crosslinking, a surface crosslinking agent solution containing 0.4 parts by mass of 1,4-butanediol, 0.6 parts by mass of propylene glycol, 2.8 parts by mass of deionized water (ion exchange water), and 0.01 parts by mass of 10% polyoxyethylene (20) sorbitan monostearate was added and uniformly mixed. Except for this, the same operation as in Example 8 was performed. The surface crosslinked water absorbent obtained was used as water absorbent (12). The properties of the water absorbent (12) are shown in Tables 1 and 2.

[0477] [Example 13]

[0478] On the basis of Example 8, (1) instead of adding a diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na) aqueous solution, 5.16 g (4.99 mmol% relative to the unsaturated monomer containing a carboxyl group) of a 2.0 wt% aqueous solution of 3-hydroxy-2,2'-iminodisuccinic acid 4-sodium (HIDS) (manufactured by Nippon Shokubai Co., Ltd.) was added; (2) when the monomer aqueous solution (b') reached 39.3°C, 4.39 g of 1 wt% polyoxyethylene (20) dehydrated sorbitan monostearate (manufactured by Kao Corporation) was added to the monomer aqueous solution. (b'); (3) instead of adding 18.4 g of 4.5 mass % sodium persulfate aqueous solution, 14.01 g of 5.9 mass % sodium persulfate was added; (4) the die aperture during grinding with a meat grinder was changed from 6.4 mm to 9.5 mm; (5) relative to 100 mass parts of the water absorbent (b) before surface crosslinking, a surface crosslinking agent solution containing 0.6 mass parts of ethylene carbonate, 2.7 mass parts of deionized water (ion exchange water), and 0.01 mass parts of 10 mass % polyoxyethylene (20) sorbitan monostearate was added and uniformly mixed. Except for this, the operation was carried out in the same manner as in Example 8. The surface crosslinked water absorbent obtained was used as the water absorbent (13). The properties of the water absorbent (13) are shown in Tables 1 and 2.

[0479] [Example 14]

[0480] In Example 3, (1) instead of adding 1.55 g of a 50% by mass D,L-malic acid aqueous solution (manufactured by Fuso Chemical Industry Co., Ltd., food additive grade), 1.12 g of a 60% by mass sodium lactate aqueous solution (manufactured by Puracal) was added (0.10 mol % relative to the unsaturated monomer containing a carboxyl group); (2) relative to 100 parts by mass of the water absorbent (b) before surface crosslinking, a surface crosslinking agent solution containing 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, 0.02 parts by mass of DENACOL (trade name) and 2.1 parts by mass of deionized water was added and uniformly mixed, and the heating treatment time during surface crosslinking was shortened by about 5 minutes. Other than that, the same operation as in Example 3 was performed. The surface crosslinked water absorbent obtained was used as water absorbent (14). The properties of the water absorbent (14) are shown in Tables 1 and 2.

[0481] [Example 15]

[0482] The same method as in Example 2 was followed until classification, to obtain a water-absorbing agent (b) before surface cross-linking in a randomly fragmented state that passed through a sieve with a mesh size of 710 μm but remained on a sieve with a mesh size of 150 μm, and a fine powder (c-1) that passed through a sieve with a mesh size of 150 μm.

[0483] Then, in addition to Example 2, a surface crosslinking agent solution containing 0.6 parts by mass of ethylene carbonate, 2.7 parts by mass of deionized water (ion exchange water), and 0.01 parts by mass of 10% polyoxyethylene (20) sorbitan monostearate was added to 100 parts by mass of the water absorbing agent (b) before surface crosslinking, and the mixture was uniformly mixed. Except for this, a heat treatment was performed in the same manner as in Example 2 to perform surface crosslinking.

[0484] Next, the mixture was classified using two JIS standard sieves with mesh sizes of 710 μm and 150 μm, respectively. This operation provided a surface-crosslinked water absorbent (d) that passed through the sieve with a mesh size of 710 μm but remained on the sieve with a mesh size of 150 μm, and a fine powder (c-2) that passed through the sieve with a mesh size of 150 μm.

[0485] Next, the fine powder (c-1) and the fine powder (c-2) were mixed in a ratio of 17:3 (w:w) to obtain fine powder (c-3). The D50 (mass average particle size) of the fine powder (c-3) was 85 μm. Next, 60 parts by mass of the fine powder (c-3) were heated to 70°C, put into a food grinder (MK-K48P, manufactured by Panasonic), and 49 parts by mass of deionized water adjusted to 80°C was added while stirring and mixed for 30 seconds to obtain granulated gel (c-3).

[0486] Next, after 1 minute from the start of granulation, 80 parts by mass of granulated gel (c-3) was added to 320 parts by mass of the granulated water-containing gel (b) obtained by repeating the operation of Example 2. Immediately thereafter, the mixture was mixed for 10 seconds using a mortar stirrer (manufactured by Nishi-Nippon Testing Equipment Co., Ltd.) heated to 80°C, thereby obtaining a mixed gel (c-4). Here, the temperatures of the granulated gel (c-3) and the granulated water-containing gel (b) before mixing using the mortar stirrer were 55°C and 50°C, respectively. In addition, the granulated gel (c-3) and the granulated water-containing gel (b) in the mortar stirrer had good miscibility.

[0487] Next, the mixed gel (c-4) was spread on a 50-mesh metal net, dried with hot air at 190°C for 30 minutes, and the dried product was crushed with a roll mill (WML type roll mill, manufactured by Inoguchi Giken Co., Ltd.), and then classified with two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. By this operation, a surface-crosslinked water-absorbing agent (c-4) was obtained in a random crushed state that passed through the sieve with a mesh size of 710 μm but remained on the sieve with a mesh size of 150 μm.

[0488] A surface crosslinking agent solution containing 0.6 parts by mass of ethylene carbonate, 2.7 parts by mass of deionized water (ion exchange water), and 0.01 parts by mass of 10% polyoxyethylene (20) sorbitan monostearate was added to 100 parts by mass of the water absorbent (c-4) before surface crosslinking, and the mixture was uniformly mixed. The mixture was then heated at 200° C. for 35 to 55 minutes to perform surface crosslinking.

[0489] Next, the mixture was classified using two JIS standard sieves with mesh sizes of 710 μm and 150 μm. By this operation, a surface cross-linked water absorbent (c-4) was obtained which passed through the sieve with a mesh size of 710 μm but remained on the sieve with a mesh size of 150 μm. The surface cross-linked water absorbent (c-4) obtained by the above method was used as a water absorbent (15). The properties of the water absorbent (15) are shown in Tables 1 and 2.

[0490] <Test results 1: Evaluation of wearing by testers>

[0491] In order to compare the stuffiness felt by diaper wearers when wearing diapers before absorbing urine, test subjects performed wearing evaluations using the water absorbing agent 1 of Example 1 and the comparative water absorbing agent 1 of Comparative Example 1.

[0492] First, a polyethylene film 150 mm wide and 500 mm long was unfolded, and a spray adhesive was sprayed on the surface, and then 20.0 g of a water absorbent was evenly spread to fix the water absorbent. Then, 7.0 g of wood pulverized pulp was spread as evenly as possible on the water absorbent from above and fixed on the polyethylene film to prepare a simulated absorbent.

[0493] A liquid-impermeable polypropylene back liner (liquid-impermeable liner) having so-called crepe lace and a liquid-permeable polypropylene front liner (liquid-permeable liner) were removed from commercially available adult diapers. Then, the simulated absorbent was arranged so that the pulp side of the simulated absorbent was located on the front liner side and the polyethylene film of the simulated absorbent was located on the back liner side, and each was fixed with a double-sided tape, thereby preparing simulated absorbent articles (i.e., diapers). The simulated absorbent article 1 was prepared using the water absorbent 1 of Example 1, and the comparative simulated absorbent article 1 was prepared using the comparative water absorbent 1 of Comparative Example 1.

[0494] In a blind test, 10 test subjects were asked to wear the two simulated absorbent articles prepared as above. The test subjects were asked to wear underwear and sportswear after wearing the simulated absorbent articles, and to walk for 10 minutes after the test started. After 10 minutes, the test subjects were asked to tell which simulated absorbent article gave them a lower sense of stuffiness or discomfort, for relative comparison. The results are shown below.

[0495] [Evaluation results of usage experience]

[0496] (1) The user experience of the simulated absorbent article 1 was better: 7 people.

[0497] (2) The comparison simulated absorbent article 1 was more comfortable to use: 1 person.

[0498] (3) Not sure which one is better: 2 people.

[0499] As shown above, 7 out of 10 test subjects answered that the absorbent article containing a water-absorbing agent with a low moisture absorption rate (simulated absorbent article 1) gave them less stuffiness or discomfort. When walking for 10 minutes immediately after wearing, the humidity in the simulated absorbent article should have increased due to the increase in body temperature and sweating. However, it was found that the absorbent containing a water-absorbing agent with a low moisture absorption rate successfully suppressed the discomfort even in the absorbent body and absorbent article with a low pulp ratio.

[0500] <Test results 2>

[0501] The evaluation results of Examples and Comparative Examples are shown in Tables 1 to 4 below.

[0502] (Table 1)

[0503]

[0504] (Table 2)

[0505]

[0506] (Table 3)

[0507]

[0508] (Table 4)

[0509]

[0510] As shown in Tables 1 to 4, the water absorbing agent of the present invention can maintain good physical properties and reduce the speed of color change over time despite having a large specific surface area.

[0511] For example, it can be seen from Comparative Examples 1 and 2 that if the specific surface area of ​​the water absorbent increases and the moisture absorption rate increases, the discoloration rate will increase. It can be seen from Comparative Examples 3 and 4 that if the amount of α-hydroxycarboxylic acid (salt) added increases, although the discoloration rate decreases, the physical properties will decrease. It can be seen from Examples 1 to 5 that by adjusting the balance between the amount of α-hydroxycarboxylic acid (salt) added and the amount of aminocarboxylic acid chelating agent added, it is possible to maintain good physical properties and reduce the discoloration rate. In Comparative Examples 5 and 6, by adjusting the balance between the amount of α-hydroxycarboxylic acid (salt) added and the amount of aminocarboxylic acid chelating agent added, although good physical properties can be maintained, the discoloration rate is not improved. It can be seen from Examples 7 to 9 that regardless of the type of α-hydroxycarboxylic acid (salt), the discoloration rate can be reduced. It can be seen from Example 10 that as long as the amount of α-hydroxycarboxylic acid (salt) and aminocarboxylic acid chelating agent added does not exceed the optimal range, the discoloration rate can be reduced even if the aminocarboxylic acid chelating agent is added after the process.

[0512] As can be seen from Example 11, even if the aminocarboxylic acid chelating agent is changed to a phosphorus chelating agent, it is possible to maintain good physical properties and reduce the discoloration rate. As can be seen from Examples 12 and 13, regardless of the type of the aminocarboxylic acid chelating agent, the discoloration rate can be reduced. As can be seen from Example 15, even if the water absorbing agent contains a granulated product obtained by recycling the fine powder generated in the water absorbing agent manufacturing process, it is possible to maintain good physical properties and reduce the discoloration rate.

[0513] As shown in Tables 1 and 2, according to Comparative Example 5 and Example 7, even the simulated absorbents assumed to be actually used have a significant difference in color changeability as when the water absorbing agent is used alone.

[0514] As shown in the above "<Test results 1: Testers' evaluation of wearing>", 7 out of 10 testers answered that the absorbent article containing a water-absorbing agent with a low moisture absorption rate (simulated absorbent article 1) gave less stuffiness or discomfort. If the user walks for 10 minutes immediately after wearing the article, the humidity in the simulated absorbent article should increase due to the increase in body temperature and sweating. However, it was found that the absorbent containing a water-absorbing agent with a low moisture absorption rate successfully suppressed the discomfort even in the absorbent body and absorbent article with a low pulp ratio.

[0515] Figure 1 This is a graph showing the relationship between the amount of α-hydroxycarboxylic acid (salt) extracted and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted in Examples and Comparative Examples. Figure 1 In the equation, the constant function x1=0.33 and the quadratic function y1=28.7x1 2 -11.1x1+1.07 defines the range of performance (physical properties or discoloration over time) that the water absorbent should satisfy in actual use. Among the examples and comparative examples, the water absorbents plotted on the right side of the constant function are comparative examples 3 and 4, so the right side area is an area with poor physical properties. In addition, the water absorbents plotted on the lower side of the quadratic function are comparative examples 2, 5, and 6, so the lower side area is an area with a fast discoloration rate over time.

[0516] Figure 2 The graphs show "CRC / AAP" and "CRC / SFC" of the water absorbing agents of Examples and Comparative Examples. Compared with the case where CRC, AAP, and SFC are evaluated separately, the evaluation method using "CRC / AAP" and / or "CRC / SFC" can more accurately evaluate the physical properties of the water absorbing agent.

[0517] The graphs of "CRC / AAP" and "CRC / SFC" each show a linear function. This linear function defines the range of performance that the water absorbent should satisfy in actual use. If the plotted physical property is below the straight line, it means that the physical property of the water absorbent is poor.

[0518] Based on Patent Document 2 (WO2017 / 170604), the water absorbent described in the examples was prepared and the specific surface area of ​​the water absorbent before surface crosslinking was measured. The result was that the water absorbent with the largest specific surface area in Patent Document 2 had a specific surface area of ​​only 30 m 2 / kg (Example 20 in Patent Document 2), and the specific surface areas of the water-absorbing agents in other examples before cross-linking were all lower than 32 m 2 / kg. In the present invention, in order to give the absorbent used in the thin diaper a sufficient humidity control function, it is necessary to control the specific surface area of ​​the water absorbent before surface cross-linking to 32m 2 / kg or more, so the water absorbent of Patent Document 2 is not suitable for thin diapers. In other words, the prior art cannot control the specific surface area of ​​the water absorbent before surface cross-linking to the extent required by the present invention. In addition, the prior art documents do not recognize that the increase in the specific surface area of ​​the water absorbent will increase the moisture absorption rate, thereby increasing the color change rate over time, which is the problem to be solved by the present invention.

[0519] (Industrial Applicability)

[0520] The water absorbing agent of the present invention can be preferably used in, for example, diapers. In addition, the water absorbing agent of the present invention can also be preferably used in various applications such as absorbent articles other than diapers (sanitary napkins, incontinence pads, etc.), agricultural and horticultural soil water retention agents, and industrial water-stopping agents.

Claims

1. An absorbent body comprising a hydrophilic substrate and a water absorbing agent, wherein: The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles. The plotted points obtained by plotting the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined in the following (a) or (b), and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120 mg / g / hr or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol% and less than 0.41 mol% relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, and the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is more than 0 mmol% and less than 20 mmol%.

2. An absorbent comprising a hydrophilic substrate and a water absorbing agent, wherein: The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles. The plotted points are within the range defined in (a) or (b) below, with the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent x1 (mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent y1 (mmol%) as the Y-axis. The specific surface area of ​​the water absorbing agent is 32 m 2 / kg or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol% and less than 0.41 mol% relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, and the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is more than 0 mmol% and less than 20 mmol%.

3. The absorbent body according to claim 1 or 2, wherein: The ratio of the mass of the water absorbing agent to the mass of the absorbent body is 75 mass % or more and 99 mass % or less.

4. The absorbent body according to claim 1, wherein The moisture absorption rate is greater than 130.3 mg / g / hr.

5. The absorbent body according to claim 1, wherein The moisture absorption rate is greater than 135 mg / g / hr.

6. The absorbent body according to claim 1, wherein The moisture absorption rate is 150 mg / g / hr or more.

7. The absorbent body according to claim 1, wherein The moisture absorption rate is 190 mg / g / hr or less.

8. The absorbent body according to claim 1, wherein The moisture absorption rate is 175 mg / g / hr or less.

9. The absorbent body according to claim 1, wherein: The moisture absorption rate is 160 mg / g / hr or less.

10. The absorbent body according to claim 2, wherein: The specific surface area is 36m 2 / kg or more.

11. The absorbent body according to claim 2, wherein: The specific surface area is 39.1 m 2 / kg or more.

12. The absorbent body according to claim 2, wherein: The specific surface area is 40m 2 / kg or more.

13. The absorbent body according to claim 2, wherein: The specific surface area is 44m 2 / kg or more.

14. The absorbent body according to claim 2, wherein: The specific surface area is 48m 2 / kg or more.

15. The absorbent body according to claim 2, wherein: The specific surface area is 52m 2 / kg or more.

16. The absorbent body according to claim 2, wherein: The specific surface area is 56m 2 / kg or more.

17. The absorbent body according to claim 2, wherein: The specific surface area is 60m 2 / kg or more.

18. The absorbent body according to claim 2, wherein: The specific surface area is 100m 2 / kg or less.

19. The absorbent body according to claim 2, wherein: The specific surface area is 80m 2 / kg or less.

20. The absorbent body according to claim 2, wherein: The specific surface area is 70m 2 / kg or less.

21. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.33 mol% or less.

22. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.30 mol% or less.

23. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.27 mol% or less.

24. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.15 mol% or less.

25. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent exceeded 0 mol%.

26. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.03 mol% or more.

27. The absorbent body according to claim 1, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.06 mol% or more.

28. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.33 mol% or less.

29. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.30 mol% or less.

30. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.27 mol% or less.

31. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.15 mol% or less.

32. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent exceeded 0 mol%.

33. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.03 mol% or more.

34. The absorbent body according to claim 2, wherein: The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.06 mol% or more.

35. The absorbent body according to claim 1, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent exceeds 0 mmol%.

36. The absorbent body according to claim 1, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.05 mmol% or more.

37. The absorbent body according to claim 1, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.10 mmol% or more.

38. The absorbent body according to claim 1, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.40 mmol% or more.

39. The absorbent body according to claim 1, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 10 mmol% or less.

40. The absorbent body according to claim 1, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 7.5 mmol% or less.

41. The absorbent body according to claim 1, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 5.0 mmol% or less.

42. The absorbent body according to claim 1, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 1.20 mmol% or less.

43. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent exceeds 0 mmol%.

44. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.05 mmol% or more.

45. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.10 mmol% or more.

46. ​​The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.40 mmol% or more.

47. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 10 mmol% or less.

48. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 7.5 mmol% or less.

49. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 5.0 mmol% or less.

50. The absorbent body according to claim 2, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 1.20 mmol% or less.

51. The absorbent body according to claim 1 or 2, wherein: The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt), glycolic acid (salt), tartaric acid (salt), citric acid (salt) or mandelic acid (salt).

52. The absorbent body according to claim 1 or 2, wherein: The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt) or glycolic acid (salt).

53. The absorbent body according to claim 1 or 2, wherein: The aminocarboxylic acid chelating agent is diethylenetriamine 5-acetic acid 3-sodium.

54. The absorbent body according to claim 1 or 2, wherein: The phosphorus chelating agent is ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), nitriloacetic acid-di(methylene phosphinic acid), nitrilodiacetic acid-(methylene phosphinic acid), nitriloacetic acid-β-propionic acid-methylene phosphinic acid, nitrilotri(methylene phosphinic acid), cyclohexanediaminetetra(methylene phosphinic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylene phosphinic acid), ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), polymethylenediaminetetra(methylene phosphinic acid), diethylenetriaminepenta(methylene phosphinic acid), 1-hydroxyethylidene diphosphinic acid or salts thereof.

55. The absorbent body according to claim 1 or 2, wherein: The ratio of the mass of the water absorbing agent to the mass of the absorbent body is 80 mass % or more and 99 mass % or less.

56. A water absorbing agent, It contains surface cross-linked randomly broken water-absorbent resin particles. The plotted points obtained by plotting the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined in the following (a) or (b), and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is 120 mg / g / hr or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol% and less than 0.41 mol% relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, and the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is more than 0 mmol% and less than 20 mmol%.

57. A water absorbing agent, It contains surface cross-linked randomly broken water-absorbent resin particles. The plotted points are within the range defined in (a) or (b) below, with the amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent x1 (mol%) as the X-axis and the amount of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent y1 (mmol%) as the Y-axis. The specific surface area of ​​the water absorbing agent is 32 m 2 / kg or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol% and less than 0.41 mol% relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, and the amount of the aminocarboxylic acid chelating agent and / or phosphorus chelating agent added is more than 0 mmol% and less than 20 mmol%.

58. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 40 or less before and after the following color change test, and a WI value of 42 or more before the following color change test; The discoloration test is as follows: the water absorbent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

59. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent satisfies the relationship of formula (3) and / or formula (4), y2≥0.24x2+18…(3), z2≥-10x2+306…(4), In formulas (3) and (4), x2 represents CRC, y2 represents AAP, z2 represents SFC, and x2 is a value greater than or equal to 26 and less than or equal to 32. The above CRC is the absorption capacity without pressure measured in accordance with the 2015 edition of NWSP 241.0.R2 (15), and its unit is g / g. The AAP is the absorption under pressure measured at a pressure of 4.83 kPa according to the 2015 edition of NWSP 242.0.R2 (15), and its unit is g / g. The above SFC is the conductivity of saline solution obtained by the following formula (a), and its unit is ×10 -7 cm 3 ·s·g -1 , SFC = (Fs(T = 0) × L0) / (ρ × A × ΔP) Formula (a) In formula (a), Fs(T=0) is the initial flow rate, in g / s, of a gel layer obtained by swelling the water absorbent in artificial urine under a load of 2.1 kPa, and a 0.69 mass % sodium chloride aqueous solution is allowed to permeate at a constant hydrostatic pressure while the gel layer is subjected to a load of 2.1 kPa. L0 is the height of the gel layer, in cm. ρ is the density of 0.69 mass % sodium chloride aqueous solution, and its unit is g / cm 3 , A is the area of ​​the top surface of the gel layer, in cm 2 , ΔP is the hydrostatic pressure applied to the gel layer, and its unit is dyne / cm 2 , The artificial urine is obtained by dissolving 0.25 g of calcium chloride dihydrate, 2.0 g of potassium chloride, 0.50 g of magnesium chloride hexahydrate, 2.0 g of sodium sulfate, 0.85 g of diammonium hydrogen phosphate and 0.15 g of diammonium hydrogen phosphate in 994.25 g of pure water.

60. The water absorbing agent according to claim 56, wherein The moisture absorption rate is greater than 130.3 mg / g / hr.

61. The water absorbing agent according to claim 56, wherein The moisture absorption rate is greater than 135 mg / g / hr.

62. The water absorbing agent according to claim 56, wherein The moisture absorption rate is 150 mg / g / hr or more.

63. The water absorbing agent according to claim 56, wherein The moisture absorption rate is 190 mg / g / hr or less.

64. The water absorbing agent according to claim 56, wherein The moisture absorption rate is 175 mg / g / hr or less.

65. The water absorbing agent according to claim 56, wherein The moisture absorption rate is 160 mg / g / hr or less.

66. The water absorbing agent according to claim 57, wherein The specific surface area is 36m 2 / kg or more.

67. The water absorbing agent according to claim 57, wherein The specific surface area is 39.1 m 2 / kg or more.

68. The water absorbing agent according to claim 57, wherein The specific surface area is 40m 2 / kg or more.

69. The water absorbing agent according to claim 57, wherein The specific surface area is 44m 2 / kg or more.

70. The water absorbing agent according to claim 57, wherein The specific surface area is 48m 2 / kg or more.

71. The water absorbing agent according to claim 57, wherein The specific surface area is 52m 2 / kg or more.

72. The water absorbing agent according to claim 57, wherein The specific surface area is 56m 2 / kg or more.

73. The water absorbing agent according to claim 57, wherein The specific surface area is 60m 2 / kg or more.

74. The water absorbing agent according to claim 57, wherein The specific surface area is 100m 2 / kg or less.

75. The water absorbing agent according to claim 57, wherein The specific surface area is 80m 2 / kg or less.

76. The water absorbing agent according to claim 57, wherein The specific surface area is 70m 2 / kg or less.

77. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.33 mol% or less.

78. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.30 mol% or less.

79. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.27 mol% or less.

80. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.15 mol% or less.

81. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent exceeded 0 mol%.

82. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.03 mol% or more.

83. The water absorbing agent according to claim 56, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.06 mol% or more.

84. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.33 mol% or less.

85. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.30 mol% or less.

86. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.27 mol% or less.

87. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.15 mol% or less.

88. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent exceeded 0 mol%.

89. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.03 mol% or more.

90. The water absorbing agent according to claim 57, wherein The amount of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent is 0.06 mol% or more.

91. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent exceeds 0 mmol%.

92. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.05 mmol% or more.

93. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.10 mmol% or more.

94. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.40 mmol% or more.

95. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 10 mmol% or less.

96. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 7.5 mmol% or less.

97. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 5.0 mmol% or less.

98. The water absorbing agent according to claim 56, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 1.20 mmol% or less.

99. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent exceeds 0 mmol%.

100. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.05 mmol% or more.

101. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.10 mmol% or more.

102. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 0.40 mmol% or more.

103. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 10 mmol% or less.

104. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 7.5 mmol% or less.

105. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 5.0 mmol% or less.

106. The water absorbing agent according to claim 57, wherein The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent is 1.20 mmol% or less.

107. The water absorbing agent according to claim 56, wherein The particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent is such that the mass average particle size (D50) is 250 μm or more and 600 μm or less, the proportion of particles smaller than 150 μm is 5% by mass or less, and the proportion of particles larger than 710 μm is 3% by mass or less.

108. The water absorbing agent according to claim 57, wherein Regarding the particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent, the mass average particle size (D50) is 250 μm or more and 550 μm or less, the proportion of particles smaller than 150 μm is 5% by mass or less, and the proportion of particles larger than 710 μm is 3% by mass or less.

109. The water absorbing agent according to claim 56, wherein Regarding the particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent, the mass average particle size (D50) is 250 μm or more and 500 μm or less, the proportion of particles smaller than 150 μm is 3% by mass or less, and the proportion of particles larger than 710 μm is 2% by mass or less.

110. The water absorbing agent according to claim 57, wherein Regarding the particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent, the mass average particle size (D50) is 250 μm or more and 500 μm or less, the proportion of particles smaller than 150 μm is 2% by mass or less, and the proportion of particles larger than 710 μm is 1% by mass or less.

111. The water absorbing agent according to claim 56, wherein Regarding the particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent, the mass average particle size (D50) is 250 μm or more and 450 μm or less, the proportion of particles smaller than 150 μm is 3% by mass or less, and the proportion of particles larger than 710 μm is 2% by mass or less.

112. The water absorbing agent according to claim 57, wherein Regarding the particle size distribution of the randomly crushed water-absorbing resin particles before surface cross-linking contained in the water-absorbing agent, the mass average particle size (D50) is 250 μm or more and 450 μm or less, the proportion of particles smaller than 150 μm is 2% by mass or less, and the proportion of particles larger than 710 μm is 1% by mass or less.

113. The water absorbing agent according to claim 56 or 57, wherein The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt), glycolic acid (salt), tartaric acid (salt), citric acid (salt) or mandelic acid (salt).

114. The water absorbing agent according to claim 56 or 57, wherein The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt) or glycolic acid (salt).

115. The water absorbing agent according to claim 56 or 57, wherein The aminocarboxylic acid chelating agent is diethylenetriamine 5-acetic acid 3-sodium.

116. The water absorbing agent according to claim 56 or 57, wherein The phosphorus chelating agent is ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), nitriloacetic acid-di(methylene phosphinic acid), nitrilodiacetic acid-(methylene phosphinic acid), nitriloacetic acid-β-propionic acid-methylene phosphinic acid, nitrilotri(methylene phosphinic acid), cyclohexanediaminetetra(methylene phosphinic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylene phosphinic acid), ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), polymethylenediaminetetra(methylene phosphinic acid), diethylenetriaminepenta(methylene phosphinic acid), 1-hydroxyethylidene diphosphinic acid or salts thereof.

117. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 39.5 or less before and after the following color change test, and a WI value before the following color change test of 42 or more, Discoloration test: The water absorbing agent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

118. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 39.0 or less before and after the following color change test, and a WI value of 42 or more before the following color change test. Discoloration test: The water absorbing agent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

119. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 39.0 or less before and after the following color change test, and a WI value before the following color change test of 46 or more, Discoloration test: The water absorbing agent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

120. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 39.0 or less before and after the following color change test, and a WI value of 50 or more before the following color change test. Discoloration test: The water absorbing agent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

121. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a WI value change of 39.4 or less before and after the following color change test, and a WI value before the following color change test of 44.2 or more, Discoloration test: The water absorbing agent is exposed to an environment with a temperature of 70°C ± 1°C and a relative humidity of 75 ± 1% RH for 7 days.

122. The water absorbing agent according to claim 59, wherein The x2 is a value greater than or equal to 26.4 and less than or equal to 31.

5.

123. The water absorbing agent according to claim 59, wherein The x2 is a value greater than or equal to 27.0 and less than or equal to 31.

5.

124. The water absorbing agent according to claim 59, wherein The y2 is a value greater than or equal to 24.5 and less than or equal to 30.

125. The water absorbing agent according to claim 59, wherein The y2 is a value greater than or equal to 25.0 and less than or equal to 30.

126. The water absorbing agent according to claim 59, wherein The y2 is a value greater than or equal to 26.0 and less than or equal to 30.

127. The water absorbing agent according to claim 59, wherein The y2 is a value greater than or equal to 24.7 and less than or equal to 26.

8.

128. The water absorbing agent according to claim 59, wherein The z2 is a value greater than or equal to 0 and less than or equal to 80.

129. The water absorbing agent according to claim 59, wherein The z2 is a value of 10 or more and 80 or less.

130. The water absorbing agent according to claim 59, wherein The z2 is a value of 15 or more and 80 or less.

131. The water absorbing agent according to claim 59, wherein The z2 is a value greater than or equal to 20 and less than or equal to 80.

132. The water absorbing agent according to claim 59, wherein The z2 is a value greater than or equal to 7 and less than or equal to 54.

133. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a water absorption rate (FSR) of 0.31 g / g / s or more per 1 g of the water absorbing agent relative to 20 g of physiological saline.

134. The water absorbing agent according to claim 56 or 57, wherein The water absorbing agent has a water absorption rate (FSR) of 0.36 g / g / s or more per gram of the water absorbing agent relative to 20 g of physiological saline.

135. A method for producing a water absorbing agent, The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles. The production method comprises a preparation step of preparing a monomer aqueous solution, wherein the monomer aqueous solution contains an unsaturated monomer containing a carboxyl group and acrylic acid (salt) as a main component, and at least one polymerizable internal crosslinking agent. In the preparation process, An α-hydroxycarboxylic acid (salt), an aminocarboxylic acid chelating agent and / or a phosphorus chelating agent are added to the monomer aqueous solution respectively, so that: the plotted points obtained by plotting the amount x1 (mol%) of the α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X-axis and the amount y1 (mmol%) of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent extracted from the water absorbing agent as the Y-axis are within the range defined by the following (a) or (b); and the moisture absorption rate of the water absorbing agent at a temperature of 40±1°C and a relative humidity of 75±1%RH is adjusted to be 120 mg / g / hr or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol % and less than 0.41 mol % relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent added is more than 0 mmol% and is 20 mmol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

136. A method for producing a water absorbing agent, wherein: The water absorbing agent contains surface cross-linked randomly broken water absorbing resin particles. The production method comprises a preparation step of preparing a monomer aqueous solution, wherein the monomer aqueous solution contains an unsaturated monomer containing a carboxyl group and acrylic acid (salt) as a main component, and at least one polymerizable internal crosslinking agent. In the preparation process, α-hydroxycarboxylic acid (salt), aminocarboxylic acid chelating agent and / or phosphorus chelating agent are added to the monomer aqueous solution respectively, so that: the plotted points obtained by plotting with the amount x1 (mol%) of α-hydroxycarboxylic acid (salt) extracted from the water absorbing agent as the X axis and the amount y1 (mmol%) of aminocarboxylic acid chelating agent and / or phosphorus chelating agent extracted from the water absorbing agent as the Y axis are within the range defined by the following (a) or (b); and the specific surface area of ​​the water absorbing agent is adjusted to 32 m 2 / kg or more, (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2), The amount of the α-hydroxycarboxylic acid (salt) added is more than 0 mol % and less than 0.41 mol % relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent, The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent added is more than 0 mmol% and is 20 mmol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

137. The method for producing a water absorbing agent according to claim 135 or 136, When the amount of α-hydroxycarboxylic acid (salt) extracted from the water-absorbing agent containing the surface-crosslinked randomly fragmented water-absorbing resin particles and the amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent do not fall within the range defined in (a) or (b) below, the production method comprises: A step of adding an α-hydroxycarboxylic acid (salt) and / or an aminocarboxylic acid chelating agent to the water absorbing agent so that the amount thereof satisfies the range defined in (a) or (b), (a) 0≤x1<0.19 and satisfy both the following equations (1) and (2), y1>28.7x1 2 -11.1x1+1.07…Formula (1), y1≥0…Formula (2); (b) 0.19≤x1≤0.33 and satisfies the following formula (2), y1≥0…Formula (2).

138. The method for producing a water absorbing agent according to claim 135 or 136, The method comprises controlling the specific surface area of ​​the water absorbent before surface cross-linking to 32 m 2 / kg or more process.

139. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 130.3 mg / g / hr or more.

140. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 135 mg / g / hr or more.

141. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 150 mg / g / hr or more.

142. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 190 mg / g / hr or less.

143. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 175 mg / g / hr or less.

144. The method for producing a water absorbing agent according to claim 135, wherein: The moisture absorption rate of the water absorbing agent at a temperature of 40±1° C. and a relative humidity of 75±1% RH is adjusted to be 160 mg / g / hr or less.

145. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 36 m 2 / kg or more.

146. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 39.1 m 2 / kg or more.

147. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 40 m 2 / kg or more.

148. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 44 m 2 / kg or more.

149. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 48 m 2 / kg or more.

150. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 52 m 2 / kg or more.

151. The method for producing a water absorbing agent according to claim 136, wherein: By adjusting the specific surface area of ​​the water absorbing agent to 56 m 2 / kg or more.

152. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 60 m 2 / kg or more.

153. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 100 m 2 / kg or less.

154. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 80 m 2 / kg or less.

155. The method for producing a water absorbing agent according to claim 136, wherein: The specific surface area of ​​the water absorbing agent is adjusted to 70 m 2 / kg or less.

156. The method for producing a water absorbing agent according to claim 135 or 136, wherein The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt), glycolic acid (salt), tartaric acid (salt), citric acid (salt) or mandelic acid (salt).

157. The method for producing a water absorbing agent according to claim 135 or 136, wherein The α-hydroxycarboxylic acid (salt) is malic acid (salt), lactic acid (salt) or glycolic acid (salt).

158. The method for producing a water absorbing agent according to claim 135 or 136, wherein The aminocarboxylic acid chelating agent is diethylenetriamine 5-acetic acid 3-sodium.

159. The method for producing a water absorbing agent according to claim 135 or 136, wherein The phosphorus chelating agent is ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), nitriloacetic acid-di(methylene phosphinic acid), nitrilodiacetic acid-(methylene phosphinic acid), nitriloacetic acid-β-propionic acid-methylene phosphinic acid, nitrilotri(methylene phosphinic acid), cyclohexanediaminetetra(methylene phosphinic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylene phosphinic acid), ethylenediamine-N,N'-di(methylene phosphinic acid), ethylenediamine-tetra(methylene phosphinic acid), polymethylenediaminetetra(methylene phosphinic acid), diethylenetriaminepenta(methylene phosphinic acid), 1-hydroxyethylidene diphosphinic acid or salts thereof.

160. The method for producing a water absorbing agent according to claim 136, wherein: The added amount of the α-hydroxycarboxylic acid (salt) is 0.04 mol% or more and 0.37 mol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

161. The method for producing a water absorbing agent according to claim 136, wherein: The added amount of the α-hydroxycarboxylic acid (salt) is 0.06 mol% or more and 0.33 mol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

162. The method for producing a water absorbing agent according to claim 136, wherein: The added amount of the α-hydroxycarboxylic acid (salt) is 0.08 mol% or more and 0.33 mol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

163. The method for producing a water absorbing agent according to claim 136, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent added is 0.4 mmol% or more and 18 mmol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

164. The method for producing a water absorbing agent according to claim 136, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent added is 0.8 mmol% or more and 16 mmol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

165. The method for producing a water absorbing agent according to claim 136, wherein: The amount of the aminocarboxylic acid chelating agent and / or the phosphorus chelating agent added is 0.8 mmol% or more and 14 mmol% or less relative to the amount of the carboxyl group-containing unsaturated monomer contained in the water absorbing agent.

166. An absorbent article comprising the absorbent body according to any one of claims 1 to 55.

Citation Information

Patent Citations

  • Absorbale article

    JP1984105448A

  • Water absorbent

    JP1985158861A

  • Absorbable article

    JP1990041155A

  • Pressure-resistant water-absorbing resin, paper diaper using the same and its production

    JP1999060975A

  • Water absorbent composition and absorbing article made therefrom

    JP1999241030A